Biocontrol potential and underlying mechanism of Trichoderma asperellum C15 against postharvest anthracnose of chili pepper - Jie Zhong; Rui Guo; Jia Rui Yang; Jin Chen; Xiao Gang Li; Jun Zi Zhu (Postharvest Biology and Technology, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Level terraces enhance the vertical distribution of soil organic carbon in mixed forests: microbial mechanisms and carbon fraction dynamics on the loess plateau - Zhe Li; Ning Zhang; Zi-ming Wang; Rui-kun Feng; Yi-qiao Chen; Zheng-hua Liu; Wen-fan Wang; Jia-bin Liu; Jian Wang (CATENA, 2026)

Dual-scale flower detection and homography-guided cluster matching for robotic pollination in trellised kiwifruit orchards - Leilei He; Bo Jia; Juncai Huang; Rui Li; Spyros Fountas; Longsheng Fu (Biosystems Engineering, 2026)

Photodegradation remodels plastic carbon pool: Unveiling transformation and fate of particulate, dissolved and gaseous carbon fractions - Taishuo Zhang; Rui Wang; Jian Wang; Zhengyang Shang; Jiarui Zhao; Xiaoqian Ye; Zixuan Zhang; Xinrui Zhang; Haiyu Zhang; Ziyan Li; Peng Liu; Hanzhong Jia (Water Research, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Five undescribed compounds isolated from Gerbera delavayi with their anti-inflammatory activity - Li Jiang; Yang Wang; Zeng-Dan Ran; Ding-Yan Lu; Rui-Xi Li; Jia Sun; Yong Huang; Xue Ma; Yong-Jun Li (Phytochemistry, 2026)

Balancing fermentation control and aroma complexity in semi-spontaneous kiwifruit fermentation through Saccharomyces cerevisiae inoculum level - Wanju Yan; Yuanjing Li; Zitong Zhang; Rou Cai; Sinuo Feng; Jia Han; Wangsheng Sun; Rui Cai; Zhouli Wang; Jing Guo (Food Research International, 2026)

Ascorbic acid enhanced performance of trace Cu(II)-Peroxydisulfate in oxidation of PPCPs: Mechanism and application - Xiujuan Kong; Rui Lu; Jielian Li; Yiming Qiu; Penghui Du; Kexin Tang; Jiaxi Lu; Wangdui Bianba; Yixin Hou; Yinuo Jia (Chemical Engineering Journal, 2026)

DAMPs and PAMPs driven macrophage activation in kidney injury - Jia-hui Li; Zhu-jun Wu; Wan-ting Li; Chun-yin Lv; Li Wang; Rui-zhi Tan (Tissue and Cell, 2026)

Effect of double-cropping pattern on biological yield and quality of silage corn across different cropping systems in the Hebei region - Liang Song; Min Jia; Quanguo Zhang; Jianghao Wang; Liwei Wang; Rui Guo; Yuanyuan Yan; Jianfeng Wei; Xinghua Li; Wei Song (Next Research, 2026)

Decoding lipid signatures and aroma characteristics of four Chinese traditional dark teas via integrative lipidomics, volatilomics, and quantitative descriptive analysis - Shan Zhang; Ruizhi Tang; Yunxia Wang; Ying Wang; Chuang Zhou; Rui Shen; Rui Liang; Niuniu Mao; Yinzi Chen; Nan Deng; Qinghua Zhou; Jia Li; et al. (Food Research International, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Flow velocity and turbulent kinetic energy effects on Crassostrea ariakensis larval settlement: Lab and CFD insights - Nan-nan Li; Rui-liang Fan; Long-ling Ouyang; Yuan-ge Chen; Jia-feng Fang; Wei Jiang; Nian Wei; Wei-min Quan (Estuarine, Coastal and Shelf Science, 2026)

Cyclic dynamic behavior of rockfill material in three-dimensional stress state - Jia Zhao; XueFeng Li; Rui Wang (Computers and Geotechnics, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Enhanced degradation of sulfamethoxazole in dielectric barrier discharge plasma via Zn tetrahedral site doping-mediated d-band center engineering of CoFe2O4 - Xiaojing Wang; Rui Cao; Na Huang; Mengmeng Du; Mingyao Yuan; Jia Ma; Fan Zhang; Jiaqi Jiang; Zhenxing Zeng; Yanzong Zhang; Zhilin Li; Shihuai Deng (Chemical Engineering Journal, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Equivalent emissivity correction of the blackbody on-board MWRI-RM - Dong Ke-Song; Xing Rui-Xian; Bai Chuan; XU Jing; Meng Wan-Ting; He Jia-Kai; Jiang Li-Fei (International Journal of Remote Sensing, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Synergistic integration of in situ generated Fe-S species and organohalide-respiring bacteria for complete dechlorination of carbon tetrachloride in groundwater - Boyu Jia; Rui Shen; Zhongdan Li; Yijun Mo; Yi Yang; Shanquan Wang (Water Research, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

Insights into the fate and dynamics of antibiotic resistance in multidrug-resistant Bacillus cereus during in vitro simulated gastrointestinal digestion - Wen-Li Shi; Juan Zhang; Rui Huang; Yan Qi; Juan Wang; Yu Ding; Jia-Jun Yan; Quan Zhou; Zi-Hui Chen; Zhi-Hang Chen; Ai-Min Jiang; Ling Chen; et al. (Food Research International, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Dietary ellagic acid improves glucose and lipid homeostasis with concurrent gut microbiota and serum metabolome remodeling in db/db mice - Rui-Bo Jia; Weipei Li; Pengru Yan; Chunxia Zhou; Zirui Huang; Mouming Zhao (Food Bioscience, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Bionic snail-shell-shaped evaporator featuring silver-nanoparticle-decorated carbon nanotubes for efficient solar desalination - Yutao Huang; Zhihong Chen; Xuan Wang; Xin Guan; Jia Zeng; Rui Li; Leitao Han (Chemical Engineering Journal, 2026)

Modification of Ce−Fe oxide by quenching induced trace Sn doping for accelerating chlorobenzene oxidation - Juexiu Li; Wenbo Xue; Huandan Cui; Yige Xi; Rui Zhao; Yin Liu; Zhongxian Song; Kajia Wei; Ziqiang Li; Chuanyi Fan; Kan Li; Jinping Jia (Chemical Engineering Journal, 2026)

Autophagy-augmenting peptide nanoplatform for synergistic chemo-immunotherapy against breast cancer - Chen Wei; Wei Gao; Xingyue Li; Ming Fu; Fantao Lin; Xiaoyu Zhao; Huiying Jia; Kang Zhang; Changgang Sun; Rui Wang; Jingkun Bai (Chemical Engineering Journal, 2026)

Corrigendum to “In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota” [Carbohydrate Polymers 339 (2024) 122255] - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2026)

Astronomically forced climate change during the Middle Oligocene-Early Miocene in the Pearl River Mouth Basin, Northern South China Sea - Shizhen Jia; Yanzhen Li; Mengqing Shang; Rui Liu; Linzhen Hu; Yongming Zhang; Xiuju Xing; Zi’ang Yang (Marine Geophysical Research, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Corrigendum to “Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process” [Process Safety and Environmental Protection 203 (2025) 107862] - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2026)

Enhanced water level fluctuations reduced the competitive advantage of cyanobacteria - Yan Chen; Rui Xia; Ruining Jia; Junde Ming; Kai Zhang; Jinghui Dou; Tianxiang Zhao; Xiang Li; Qin Zhang; Qi Zhang (Journal of Hydrology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

From acute defense to prolonged metabolic homeostasis: Insights into microalgae responses to PVC microplastic exposure - Jia Liang; Xiao Tan; Jiawei Li; J. Paul Chen; Yuanyuan Tang; Zhipeng Duan; Jiang Huang; Rui Zhu (Journal of Hazardous Materials, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Speleothem multi-proxy inferred hydroclimate variability during the 2.8 ka event and its influence on human activities in southeastern China - Xiaomei Zhang; Haiwei Zhang; Ashish Sinha; Miaomiao Wang; Jian Wang; Yueer Li; Liangkang Pan; Rui Zhang; Youfeng Ning; Xuexue Jia; Baoyun Zong; Hai Cheng (Global and Planetary Change, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Differential volatile-omics analysis for tamarind (Tamarindus indica L.) and aroma-active compounds identification via DMU-SPME-GC-MS method - Rui-Hua Jin; Ling Zhang; Li-Bo Qi; Chun-Mei Yuan; Zi-Bo Song; Jia-Teng Chen; Ming Du; Xian-Bing Xu (Food Chemistry, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Confined pyrolysis of single-molecule hemin anchored in the cages of zeolite imidazole frameworks toward oxygen reduction reaction - Zihui Zhai; Rui Gao; Li Yang; Qiunan Liu; Ruonan Zheng; Jia Li; Ruijie Song; Junhu Wang; Zhaoxia Hou; Jianyu Huang; Weiqiao Deng; Yujiang Song (Chemical Engineering Journal, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

The synergistic effect and underlying mechanism of bimetal and its support in cobalt‑lanthanum doped palygorskite-based catalyst for norfloxacin removal through activating persulfate - Ye Li; Jia-Hang Liu; Bai-Hang Zhao; Xu-Ming Liu; Rui-Xuan Liu (Journal of Water Process Engineering, 2026)

A new pathway to enhance the oceanic carbon sink: inorganic carbonate precipitation driven by calcium–alkali coupling - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Lei Li; Bao Xiao Qu; Qi Dong Wang; Jun Ma; Jian Wei Xing; Zhi Bo Wang; Rui Wang; et al. (Journal of Environmental Management, 2026)

Cross-instrument coal quality spectral analysis via a PDS-assisted fine-tuning calibration transfer method - Junlong Gao; Jiaxuan Li; Jiaxin Yin; Rui Gao; Zhihui Tian; Yang Zhao; Yu Bai; Lei Dong; Weiguang Ma; Lei Zhang; Wangbao Yin; Suoteng Jia (Analytica Chimica Acta, 2026)

Adaptive Fixed-Time Control Framework for Deterministic Response of Fully Constrained Vessels with Unknown Dynamics - Qiang Guo; Shuangpeng Duan; Jia Zhou; Shengguo Wang; Rui Li; Xianku Zhang (Journal of Marine Science and Engineering, 2026)
To achieve precise trajectory tracking for surface vessels subject to unknown dynamics, strict physical limitations, and external disturbances, this paper proposes an Adaptive Fixed-Time Control Framework that ensures a deterministic response under full constraints. First, navigation safety is guaranteed by employing a Barrier Lyapunov Function (BLF) to strictly confine vessel position states, enabling constrained position tracking without requiring prior knowledge of the desired trajectory. Second, addressing the input constraint aspect of the “full constraints” problem, a fixed-time auxiliary system is introduced to compensate for nonlinearities induced by actuator saturation, thereby maintaining control feasibility. Central to this framework is the realization of a deterministic response; by incorporating fixed-time convergence theory, the controller guarantees that velocity tracking errors converge within a predefined time bound independent of initial conditions. Furthermore, an RBF neural network combined with adaptive techniques is utilized to estimate unknown dynamics and external disturbance bounds online, enhancing robustness and safety in realistic marine environments.

Fe-N-C-supported LaFeO3 heterojunction electrodes for efficient copper and fluoride removal in symmetric capacitive deionization - Shaojian Xie; Yujia Wang; Rui Zhang; Lei Huang; Jia Yan; Zhenxin Chen; Hongguo Zhang; Meng Li; Hongbo Zeng (Water Research, 2026)

Dihydromyricetin attenuates LPS-induced liver injury in chicks through the JNK signaling pathway - Lina Jia; Jiarui Liu; Zhenghua Ji; Liang Yuan; Yingchao Gong; Xinru Jiang; Xianan Fan; Changwen Li; Rui Li; Haoran Wang; Fangping Liu (Research in Veterinary Science, 2026)

Effects of MFC-mediated iron tailings on heavy metals transformation and microbial communities during the aerobic composting of pig manure - Keping Li; Rui Yu; Xia Wu; Wencong Yang; Wenyue Shao; Yong Yu; Nana Luo; Jia Zhou (International Biodeterioration & Biodegradation, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

Carbonate-retaining multilayer Co(OH)2@FeOOH electrodes enable superior stability in seawater oxygen evolution: Sustaining 5000 h at 1 A cm−2 - Yingxia Wei; Zhangwei Li; Farhat Nosheen; Xueyan Wu; Rui Xue; Xingyun Li; Yan Lv; Jixi Guo; Dianzeng Jia (Chemical Engineering Journal, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Hydrogenophaga pseudoflava widely distributed in wastewater treatment plants exhibiting heterotrophic nitrification-aerobic denitrification: From characterization to genomics - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Jia-Ying Li; Ya-Nan Mi; Xin-Yu Gu (Bioresource Technology, 2026)

Does a positive culture correlate with the volume of synovial fluid inoculated into blood culture bottles for the diagnosis of periprosthetic joint infection? - Jia-Zheng Xu; Zhi-Sen Gao; Zhen Zhang; Ping Song; Wei Chai; Rui Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

An intelligent lithofacies identification method for tight carbonate reservoirs integrating dynamic clustering and BiLSTM-attention network - Guangjie Fu; Zihao Mu; Haiwei Mu; Rui Yang; Meiqi Jia; Xinyu Li (Earth Science Informatics, 2026)

Drought-induced disaster Chains: A global perspective of propagation probabilities and mitigation priorities - Huicong Jia; Fang Chen; Rui Li; Yu Chen; Lei Wang (Journal of Cleaner Production, 2026)

A machine learning approach coupling immediate and lagged drivers to predict sand and dust storms in Northern China - Mile Wang; Kunxia Yu; Peng Li; Zhanbin Li; Rui Yan; Zixia Jiang; Xue Li; Lu Jia (Journal of Environmental Management, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Strain-specific effects of infant-derived Bifidobacterium on gut microbiota modulation and mucus barrier responses in Salmonella infection - Xiaogan Zhao; Mahsa Ghahvechi Chaeipeima; Luyao Xiao; Xia Fan; Wenkai Jiang; Xiran Jia; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Bioscience, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

Nitrogen fertilization shapes rhizosphere microbiome to boost peanut yield: A two-year field study - Xiangjun Kong; Peipei Jia; Lijie Li; Ali Muhammad; Rui Wang; Aziz Khan; Jaya Nepal; Fei Li; Zhiyong Zhang (Applied Soil Ecology, 2026)

Effects of suspended sediment on the survival and settlement of Crassostrea ariakensis and Crassostrea sikamea larvae: Results from lab experiments - Nan-nan Li; Yu Han; Yuan-ge Chen; Wei-liang Dong; Long-ling Ouyang; Rui-liang Fan; Wei Jiang; Jia-feng Fang; Nian Wei; Jin-ming Wang; Wei-min Quan; Jian Zeng (Regional Studies in Marine Science, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Surface aging of Ti-based MXene attenuates mitochondrial toxicity via suppressed cellular uptake and reactivity - Rui Zhang; Xiaodi Li; Yujiao Liu; Xuan Mao; Yongyi Wei; Yu Wang; Xiaofei Zhou; Jianbo Jia (Environmental Pollution, 2026)

Assessing the spatiotemporal dynamics of wildfire drivers in Southeast Asia: An explainable spatial machine learning framework - Lei Xia; Zhixian Yang; Yongling Yang; Liang Han; Chengwen Jia; Jie Li; Wenxuan Fan; Rui Liu (Environmental Impact Assessment Review, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Nickel refining fumes activate glutamine metabolism via the HIF‐1α/Notch pathway to drive epithelial-mesenchymal transition in Beas‐2B cells - Qian-Qian Sun; Han-Nong Yu; Rui-Ze Wu; Bo Zhang; Wen-Xue Yao; Wei-Yang Liu; Jia Han; Li-Yan Ju; Yu-Lin Pan; Yong-Hui Wu (Toxicology, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

CRISPR/Cas9-mediated knockout of the 22 kDa α-prolamin genes orchestrates the regulation of functional amino acid content in foxtail millet - Rui Zhao; Jiayi Chen; Yongchao Li; Maosheng Jin; Kejin Liu; Yang Liu; Lulu Gao; Guanghui Yang; Xiangyang Yuan; Xiaoqian Chu; Jia-Gang Wang (Journal of Plant Physiology, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Probabilistic modeling of microwave thermal damage at rough rock-cement interfaces using a Bayesian-ANN framework - Jia-Le Li; Fuxin Rui; Yanlong Zheng; Gao-Feng Zhao; Kostas Senetakis (Computers and Geotechnics, 2026)

Corrosion behavior and biocompatibility of MgZnP@PDA coatings on biodegradable Zn2Cu alloy - Rui Yue; Suqin Wang; Yusong Pan; Yusheng Zuo; Xiancai Meng; Gaozhi Jia; Xiuling Lin; Run Huang; Shaoding Sheng; Lingyu Li (Chemical Engineering Journal, 2026)

CRISPR/Cas9-mediated α-prolamin gene (Seita.8G190200) mutagenesis increases the content of functional amino acids in foxtail millet (Setaria italica) - Rui Zhao; Jiayi Chen; Yongchao Li; Dan-Ying Chen; Xueting Kang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; Jia-Gang Wang (Plant Cell Reports, 2026)

Enhancing the catalytic performance of ZnZrOx/SAPO-34 bifunctional catalysts through structural modulation - Rui Xiang; Tao Du; He Jia; Yingnan Li; Peng Chen; Qiang Yue; Heming Wang; Yisong Wang (Journal of Environmental Chemical Engineering, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Study on the irradiation control of urease activity and its solidification of red clay to enhance radon reduction - Yuanyuan Tang; Rui Liang; Jia Wei; Yiqing Sun; Weihang Peng; Fubing Li; Chengyu Zhang; Changshou Hong (Journal of Environmental Radioactivity, 2026)

Seismic performance of Chinese pavilion-type timber frame with forked column: Experimental tests - Zuoshuai Sun; Hongtai Zhang; Sicheng Li; Rui Zhang; Ping Xiang; Liang-jiu Jia (Engineering Structures, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Electrocatalytic degradation of norfloxacin using biochar electrode derived from oily sludge: Synergistic effects of hydrothermal and pyrolytic treatment - Quxin Cong; Rui Jia; Juan Zhou; Lei Li; Pin Gao (Chemical Engineering Journal, 2026)

Molecular dipole engineering enabled TiO2 electron transport layers for stable quantum-dot light-emitting diodes - Hang Liu; Pei-Li Gao; Bo Li; Hui Bao; Yin-Man Song; Meng-Wei Wang; Ting Ding; Jing Jiang; Rui-Feng Zheng; Feng-Jia Fan; Hai-Zheng Zhong; Kar-Wei Ng; et al. (Chemical Engineering Journal, 2026)

Structural characterization and anti-hepatic fibrosis effects of a novel polysaccharide from Astragalus complanatus seeds - Zhi-Fan Zhu; Shu-Yao Wang; Xiao-Feng Liu; Na Liu; Dian-Chao Dong; Yan-Chun Qi; Na Li; Nan Wang; Jin Tan; Chang Jia; Rui-Qing Cai; Xiao-Qiang Li; et al. (Carbohydrate Polymers, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Exopolysaccharides from Enterococcus faecium WH strain inhibit porcine epidemic diarrhea virus infection in vitro - Chenxi Li; Xiangchao Jia; Min Su; Rui Zhou; Zili Li (Veterinary Microbiology, 2026)

GABPα2β2 tetramer deficiency impairs natural killer cell maturation, compromising cytotoxicity and resistance against melanoma - Weiwei Jia; Wanting Zhong; Shanshan Hao; Zhao Wang; Shuaishuai Niu; Yingdi Xu; Yajiao Zhang; Mingxia Feng; Haitao Jiang; Jiarui Zhang; Danli Song; Peiyao Yan; et al. (Science Bulletin, 2026)

Simulated Microgravity affects immune reaction to infection through altering lymphocyte differentiation, cytokine secretion, and macrophage polarization - Hongyan Cai; Rui Jia; Huimin Chen; Yingying Wu; Yaya Qin; Shaoyan Si; Lei Zhu; Xiaotong Lou; Xiangru Li (Life Sciences in Space Research, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Dietary Haematococcus pluvialis powder enhances the growth and hepatopancreas and intestinal health of Leuciscus waleckii via NF-κB/Nrf2 pathway - Bei Xi; Tong-Tong Tan; Qi Sun; Ming-Xuan Zhang; Jia-Jing Wang; Rui Zhu; Deng-Lai Li; Li-Fang Wu (Fish & Shellfish Immunology, 2026)

Comprehensive performance of iron-loaded biochar adsorption of U(VI) at an industrial scale based on life cycle assessment and economic analysis - Jia He; Zhou Shen; Yisa Li; Hao Wen; Rui Lu; Shaoli Fan; Jian Gao (Environmental Research, 2026)

A metal-immuno photosensitizer strategy: Iridium(III)-zidovudine conjugate triggering sequential organelle stress and synergizing with PD-L1 inhibitor in oral squamous cell carcinoma - Yi-Ling Li; Peng Wang; Wu-Ya Zhang; Rui Zhou; Jia-Ying Zhou; Jia-Wen Chen; Jia-Yin Wu; Bin Cheng; Cai-Ping Tan; Tong Wu (Chemical Engineering Journal, 2026)

Deciphering indoor summer microbial composition and its health impacts: a study based on university campus in Beijing - Li Guo; Hua Zhao; Rui Du; Zeyu Jia; Yuanyuan Li (Building and Environment, 2026)

Spatiotemporal dynamics of non-photosynthetic vegetation across China and their implications for carbon fluxes along climate gradients - Chunsheng Wang; Qingjiu Tian; Wenmin Zhang; Jia Tian; Lili Chang; Rui Zhang; Qianjing Li (Science China Earth Sciences, 2026)

Integrated Aerobic Exercise and Multisensory Environment Training for Age-related Cognitive Decline via Hippocampal-prefrontal Neural Circuit Modulation - Huawei Lin; Yuxi Qiu; Zhongyi Hu; Liming Chen; Yaling Dai; Tao Jiang; Rui Li; Sinuo Wang; Yajun Cao; Jianhong Li; Huanhuan Liu; Yuwei Ye; et al. (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Mechanisms of Fish Intestinal Damage Under Environmental Stress: Insights From Carbonate Saline–Alkali Water Perspective - Jia Rui Cui; Qi Fang Lai; Yue‐Hong Li (Reviews in Aquaculture, 2026)
The intestinal tract is an important functional organ in fish, as it plays a key role in digestion and absorption, mucosal immunity, endocrine function, and metabolism. Therefore, damage to this organ greatly impacts fish health. This injury is usually associated with a poor aquaculture water environment, stressful conditions, and pathogen presence. In this review, in light of gut injury being a common pathology in aquaculture, we have summarized the current understanding of the intestinal damage of fish caused by carbonate water stress, and the mechanism of intestinal tissue damage caused by carbonate saline water stress, including the intestinal barrier function of fish and the role of various cells and molecules involved in the occurrence and development of diseases. Comparative data on carbonate stress responses across different teleost lineages (such as the Cyprinidae and Perciformes) have been integrated. The review also covers current methods for treating intestinal damage in fish, including dietary interventions, medications, and probiotics. Our findings highlight the need for more in‐depth research in this area to better understand the mechanisms underlying the occurrence of intestinal tissue damage in fish in carbonate‐based saline waters and to develop effective preventive and therapeutic strategies. Improved development of saline–alkaline waters and research into new treatments are essential for the sustainability of aquaculture and the health and productivity of farmed fish.

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Biodegradable film combined with ploughing: An approach to improve the sustainability of rainfed spring maize production - Rui Qian; Luning Du; Wenjing Li; Wei Wang; Yang Zhang; Yujie Gao; Wenjing Feng; Jiaji Ding; Wenbo Lv; Pengyao Qin; Tie Cai; Xiaolong Ren; et al. (Soil and Tillage Research, 2025)

Numerical calculation of line heating for hull curved plate based on strain direct boundary - Shun Wang; Haohao Jia; Yuxuan Fu; Ji Wang; Rui Li (Ocean Engineering, 2025)

The effect of minimum temperatures on changes in river dissolved oxygen is more pronounced in the climate transition zone - Qin Zhang; Rui Xia; Kai Zhang; Haiming Li; Yan Chen; Ruining Jia; Jinghui Dou; Lina Li; Chao Yan; Xiang Li (Journal of Environmental Management, 2025)

Degradation of trichloroethylene by magnetite-activated periodate and the effect of humus on the degradation mechanism - Jiayuan Li; Shibing Jia; Lei Chen; Rui Song; Hongyong Wang; Gang Xu (Journal of Environmental Chemical Engineering, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Dual mechanisms of Vitisin A in managing alcoholic liver disease: Inhibition of lipogenesis and complement activation - Yuanqin Zhu; Huilin Deng; Jia Liu; Xusheng Li; Xin Huang; Zhaodi Che; Weibin Bai; Rui Jiao (Food and Chemical Toxicology, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Combined effects of high-fat diet feeding and Streptococcus agalactiae infection on lipid metabolism, antioxidant status, and immune response in tilapia (Oreochromis niloticus) - Rui Jia; Yiran Hou; Linjun Zhou; Chengfeng Zhang; Bing Li; Jian Zhu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Point-of-care testing of neuromyelitis optica spectrum disorder using a sonochemically enhanced bifunctional CdTe-ZIF-8 nanohybrids-labelled lateral flow immunoassay - Qing Fu; Manxia Wang; Jia Shu; Guangjun Xiao; Zhujun Ai; Xin Gao; Huan Cai; Yan Zhao; Xuhuai Fu; Zhizhong Li; Mengjie Zhang; Jinzhou Feng; et al. (Chemical Engineering Journal, 2025)

A single chitosan-based fluorescent sensor for the discriminant analysis and quantitative detection of bisulfite and oxytetracycline in real samples - Chao Gao; Rui-Xue Li; Xiang Li; Zhenxing Zhong; Jia-Hui Wang; Wei Li (Carbohydrate Polymers, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Forest greenness stability in response to climate change along forest edge–core gradients - Shaodong Huang; Rui Li; Yujie Li; Siyu Xue; Panfei Fang; Yuying Liang; Jia Wang; Longhuan Wang (Agricultural and Forest Meteorology, 2025)

Multiscale responses of gap-graded soil under the combined effect of train vibration and seepage erosion - Dong-Mei Zhang; Hui-Hao Chen; Xiao-Chuang Xie; Si-Rui Chen; Zhao-Geng Chen; Jia-Ping Li (Transportation Geotechnics, 2025)

Investigation on unrecognized catalytic contributing role of chlorobenzene oxidation by iron ore in sintering process - Juexiu Li; Wenbo Xue; Huandan Cui; Xinrui Lei; Wenlong Zhou; Rui Zhao; Ziqiang Li; Chuanyi Fan; Zhongxian Song; Jinping Jia (Process Safety and Environmental Protection, 2025)

Higher ammonia oxidizing activity of comammox cooperates with ammonia-oxidizing bacteria to release N2O in river ecological restoration areas - Yuantao Wang; Shenghua Zhang; Rui Jia; Xin He; Ang Li; Dongdan Yuan (Journal of Environmental Management, 2025)

Multiscale structural design integrating mechano-flame retardancy-superhydrophobicity into multifunctional phenolic aerogel - Zhiyan Lu; Zhipeng Liu; Zhe Hu; Li Zhao; Zhen Jia; Zebao Rui (Chemical Engineering Journal, 2025)

Amino acid-induced supramolecular assembly defective carbon nitride for efficient photocatalytic CO2 reduction - Rui Li; Liting Lai; Si Li; Shipeng Wan; Wenbei Jia; Yu Han; Ruixuan Chu; Qin Zhong; Zhaoxiang Zhong (Chemical Engineering Journal, 2025)

Prolonged sepsis triggers abnormal mitochondrial dynamics in the limb muscles and diaphragm - Chao Xiong; Fasheng Guan; Jianguo Feng; Jing Jia; Jumei Zhang; Rui Tu; Jie Li; Jun Zhou; Jianglin Wang; Li Liu (Molecular and Cellular Biochemistry, 2025)

Extreme Phenotypic Variation Confounds Acanthocephalan Systematics: A Case Study of Longicollum pagrosomi and Pomphorhynchus zhoushanensis (Acanthocephala: Echinorhynchida) - Cui‐Hong Zhao; Hui‐Xia Chen; Matthew Thomas Wayland; Rui‐Jia Yang; Xiao‐Hong Gu; Liang Li (Zoologica Scripta, 2025)
The phylum Acanthocephala is a ubiquitous group of zooparasites, with major socio‐economic importance. The true diversity of the Acanthocephala is obscured by the phenomena of cryptic speciation and a large degree of intraspecific variation. In this study we describe an example of extreme phenotypic variation in neck morphology. The pomphorhynchid acanthocephalans, Longicollum pagrosomi and Pomphorhynchus zhoushanensis were originally differentiated on the basis of differences in neck morphology; P. zhoushanensis possesses a neck bulb whereas this structure is absent in L. pagrosomi . However, ASAP and phylogenetic analyses of the ITS, 12S, cox 1 and cox 2 sequence data, together with comparative mitogenomics, revealed that the two taxa are in fact conspecific. Therefore, the presence or absence of a neck bulb represents extreme phenotypic variation, and this character is not reliable for distinguishing the genera Pomphorhynchus and Longicollum. In the absence of other characters to discriminate the two genera, Longicollum is relegated to a junior synonym of Pomphorhynchus . A new combination Pomphorhynchus pagrosomi (Yamaguti, 1935) comb. nov. is proposed for L. pagrosomi Yamaguti, 1935 and P. zhoushanensis Li, Chen, Amin & Yang, 2017 is relegated to a junior synonym of P. pagrosomi .

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Hydrological variability significantly influences aquatic biological integrity at the spatial scale in semi-arid watersheds - Lina Li; Rui Xia; Xinghui Xia; Ming Dou; Minhua Ling; Yan Chen; Jinghui Dou; Kai Zhang; Ruining Jia; Chao Yan (Journal of Hydrology, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Selective adsorptive separation of xylene isomers in vapor and liquid phases by nonporous adaptive crystals of leaning pillar[6]arenes - Yu-Xiang Sun; Susu Ren; Gengxin Wu; Xiang-Shuai Li; Haitao Wang; Jia-Rui Wu (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Enhancing soil health in urban green spaces: The critical role of terrain and hydrological connectivity in nutrient redistribution - Pengcheng Lv; Yang Liu; Xiaoli Jia; Rui Li; Honglin Zhang; Yunlong Zhai; Tianyu Zhang (CATENA, 2025)

Seasonal variation of microbial activity in atmospheric particulate matter and its lagging response to environmental factors - Hua Zhao; Rui Du; Li Guo; Yuanyuan Li; Hanlin Chen; Zeyu Jia (Atmospheric Environment, 2025)

Research on calibration transfer methods in coal quality spectral analysis across instruments and coal types - Jiaxuan Li; Jiaxin Yin; Rui Gao; Yan Zhang; Lei Zhang; Lei Dong; Weiguang Ma; Wangbao Yin; Suotang Jia (Analytica Chimica Acta, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Research progress on programmed cell death of cardiomyocytes in pressure-overload hypertrophic cardiomyopathy - Fei Xiao; Hui-Li Li; Jia-Rui Wang; Hui-Min Wu; Yu-Qi Cai; Jia-Wan Wang; Hao Che; Gang Li; Zheng-Yuan Xia; Yu-Bo Xie; Sheng Wang (Apoptosis, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Construction of multiscale high entropy oxide nanofibers and their room temperature gas-sensitive properties: a synergistic DFT theoretical and experimental study - Rui Yang; Xinmei Li; Zhiqi Yan; Liming Jia (Chemical Engineering Journal, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Nested MPI-CWRF dynamical downscaling and future projections of summer extreme precipitation changes in China - Huan Li; Fengxue Qiao; Nan Wei; Haoran Xu; Rui Wang; Fulin Jiang; Guimin Lou; Jia Zhao; Qingyu Yang (Frontiers of Earth Science, 2025)

The synergistic effects of entomopathogenic fungus Cordyceps javanica and parasitoid Tamarixia radiata in Asian citrus psyllid management - Pei-Ping Xu; Xin-Yi Chen; Jia-Rui Wang; Zi-Tong Lu; Marguerite Mukangango; Wen-Sang; Bao-Li Qiu; Li-He Zhang; Shaukat Ali (Crop Protection, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Vermicompost maintains topsoil fertility by reducing NH3 volatilization and improving 15N/NO3- retention in a saline-alkali soil - Siping LI; Chong WANG; Huiying HUANG; Jia CAO; Rui XUE; Binglei WANG (Pedosphere, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Source analysis of soil selenium and evaluation of soil environmental quality and safety in the eastern area of Zichuan District, Shandong Province - Jia-Wen Cui; Li-Yuan Yang; Jie-Rui Dai; Xi-Qiang Zhao; Jia-Liang Li (Environmental Monitoring and Assessment, 2025)

Unveiling anomalies in visual processing regions in obsessive-compulsive disorder: evidence from gray matter volume and functional connectivity analyses - Rui Liu; Fengxia Zhang; Pengchong Wang; Jia Luo; Yue Liu; Kaiyin Huang; Xiangyun Yang; Aihong Yu; Zhanjiang Li (Brain Imaging and Behavior, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Neuroprotective lindenane sesquiterpenoids from the roots of Lindera aggregata (Sims) Kosterm - Lie-Feng Ma; Shan-Rong Luo; Qian-Qing Liu; Rui-Si Tang; Ning-Yu Chen; Di Luo; Lu Guo; Jia Li; Rui Wu; Zha-Jun Zhan (Phytochemistry, 2025)

Alterations in microbial-mediated methane, nitrogen, sulfur, and phosphorus cycling within paddy soil induced by integrated rice-fish farming - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Sun Wei; Bing Li; Jian Zhu (Journal of Environmental Management, 2025)

An improved direct analysis method of transmission towers incorporating geometric defects and bolt slippage effects - Yu Zhu; Hong-Nan Li; Xing Fu; Jia-Xiang Li; Rui-Zeng Wei (Engineering Structures, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Linking gut microbiome profiles and white matter integrity to social behavior in young autistic children: from the perspective of individual variation - Xinyue Huang; Weixing Zhao; Rui Feng; Yuanyue Zhou; Jia Wang; Jinming Xiao; Lei Li; Xiaolong Shan; Yu Feng; Yating Ming; Jing Cao; Xiaodong Kang; et al. (Science Bulletin, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

A novel model for predicting the ultimate bending moment of subsea pipelines with corrosion-dent coupled defects - Fuheng Hou; Yanfei Chen; Lusheng Jia; Zengli Peng; Yu Liu; Ruihao Liu; Rongfeng Zhong; Rui Li (Ocean Engineering, 2025)

Wastewater surveillance for chronic disease drugs in wastewater treatment plants: Mass load, removal, and sewage epidemiology - Li Yao; Yang Hu; Jia-Hui Yang; Rui Wu; Fei-Long Chen; Xi Zhou (Journal of Hazardous Materials, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

Arsenolipid-induced reproductive toxicity in Caenorhabditis elegans: Elucidating the mechanism through the HUS-1-CEP-1-EGL-1-CED-9-CED-4-CED-3 signaling pathway - Caiyan Li; Zhuo Wang; Bingbing Song; Kit-Leong Cheung; Jianping Chen; Rui Li; Xiaofei Liu; Xuejing Jia; Qiaoli Zhao; Saiyi Zhong (Food and Chemical Toxicology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Microfluidic-oriented assembly of MXene composite fibers for flexible zinc ion supercapacitors with high energy density - Fanyu Xie; Yuan Du; Menghan Chu; Xiaoyu Jia; Hui Cao; Rui Zhang; Hongwei Li; Mei Zhang (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Identification of Age-Related Characteristic Genes Involved in Severe COVID-19 Infection Among Elderly Patients Using Machine Learning and Immune Cell Infiltration Analysis - Huan Li; Jin Zhao; Yan Xing; Jia Chen; Ziying Wen; Rui Ma; Fengxia Han; Boyong Huang; Hao Wang; Cui Li; Yang Chen; Xiaoxuan Ning (Biochemical Genetics, 2025)

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Algicidal activity and mechanism of novel Bacillamide a derivative against red tide algae Skeletonema costatum and Prorocentrum minimum - Huili Li; Xiaoxue Li; Yi Liu; Ronglian Xing; Hongxia Zhang; Wenguang Jia; Lihong Chen; Rui Li; Zhen Yu; Zhihong Tang (Pesticide Biochemistry and Physiology, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Adaptive sowing window strategy for improving grain filling and water loss characteristics of film-mulched maize in Northwest China - Xudong Zhang; Haixiang Xiong; Rui Wang; Junjie Li; Zhaoyun Dong; Zhikuan Jia; Qingfang Han (Field Crops Research, 2025)

Integrated rice-fish farming dynamically altered the metal resistances and microbial-mediated iron, arsenic, and mercury biotransformation in paddy soil - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Wei Sun; Bing Li; Jian Zhu (Environmental Pollution, 2025)

Portable intelligent digital microfluidic system for rapid antibiotic susceptibility testing - Caiwei Li; Yibo Qi; Stephanie Andaluz; Nan Shi; Yan Lu; Pui-in Mak; Rui P. Martins; Yanwei Jia (Chemical Engineering Journal, 2025)

ZnCo2O4/LaAlO3 transparent pn junction towards enhanced photoelectric response and stability via interfacial homogeneous high entropy oxide perovskite La(Cu0.2Co0.2Ni0.2Fe0.2Mn0.2)O3 QDs - Bo He; Yujia Huang; Rui Wang; Dingwei Wang; Chengyu Jia; Jun Cao; Lei Shi; Jiaqi Pan; Zhiguo Zhao; Chaorong Li (Chemical Engineering Journal, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Green Manure Coupled With Straw Returning Increases Soil Organic Carbon via Decreased Priming Effect and Enhanced Microbial Carbon Pump - Guopeng Zhou; Guilong Li; Hai Liang; Rui Liu; Zhengbo Ma; Songjuan Gao; Danna Chang; Jia Liu; David R. Chadwick; Davey L. Jones; Weidong Cao (Global Change Biology, 2025)
Green manuring and crop straw returning are widely used to increase soil organic carbon (SOC) sequestration, while the pathways and drivers in native SOC mineralization and new SOC formation after implementing these practices remain unclear. Here, through a 10‐locations' network field experiment in southern China, the effects of green manuring (Mv), rice straw returning (Rs), and their combination (MR) on soil C sequestration efficiency (CSE) were evaluated. A microcosmic experiment was performed to trace the components and participants of SOC mineralization and formation under the three practices. The network experiment showed that Mv, Rs, and MR annually improved SOC stock by 119.7, 477.0, and 830.2 kg C ha −1 , respectively, with MR having the highest CSE of 23.1%, followed by Rs (17.7%) and Mv (13.3%). The microcosmic experiment further revealed that the highest CSE in MR most likely resulted from the low mineralization of native SOC (positive priming effects, PE) and great formation of new SOC through microbial C pump (MCP). Therein, MR mainly downregulated the K‐strategists of the microbial community (e.g., Gaiellales ) to yield negative PE on recalcitrant native SOC, such as protein/amino sugar‐ and lignin‐like molecules; meanwhile, MR had the highest bacterial and fungal MCPs, which were, respectively, led by r‐strategists (e.g., Sporobacter ) and molds (e.g., Cladosporium ). The study highlights the advantages of mixing low‐ (Rs) and high‐quality (Mv) residues for efficiently increasing SOC sequestration and firstly discovers the core microbes that dominate the mineralization and formation of SOC in paddy fields.

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

Catalyst pre-diffusion: An efficient strategy for the construction of COF nanofiltration membranes - Lin Yu; Aida Aibulatova; Zhen-Liang Xu; Li Li; Changqing Hao; Rui Jia; Yin-Xin Fang; Yan Zheng; Yong-Jian Tang (Desalination, 2025)

Spatio-temporal variability of surface phytoplankton community structure in relation to different water systems in the east China sea coast - Anglu Shen; Shuaishuai Su; Haowen Li; Wei Kang; Rui Jia (Continental Shelf Research, 2025)

Carboxymethyl chitosan/oxidized hyaluronic acid hydrogel-encapsulated hucMSC-derived exosomes for enhanced hepatic regeneration and post-hepatectomy applications - Qiuxia Zheng; Jia Yao; Zongbin Sun; Rui Li; Yue Zhang; Pan Jiang; Ye Xie; Xiaojing Song; Hongfa Sun; Dan Zhu; Haixu Ni; Xun Li (Carbohydrate Polymers, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

“Off-on-off”-based metal-organic framework fluorescent sensor for adenosine triphosphate detection and tumor microenvironment-triggered drug release - Tianqian Jia; Ke Wang; Xiaojuan Li; Cuixia Ma; Du Yang; Rui Wang; Yanyan Zhang; Sicheng Zhai; Shuming Li (Analytica Chimica Acta, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Monitoring dust retention variations in different functional zones based on leaf magnetism and the influence of green belt spatial layouts on leaf dust retention - Ziwei Tao; Shuxuan Li; Bo Wang; Yi Xie; Rui Wang; Linglin Hu; Jia Jia; Junhui Zhang (Environmental Monitoring and Assessment, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Enhanced regeneration of large segmental bone defects via hierarchically structured bioactive scaffolds - Mo-Han Wang; Shao-Meng Wen; Yun-Hong Cong; Huai-Ling Gao; Xian-Yu Zheng; Zi-Xiang Han; Run Wang; Rui Xu; Lu Yang; Wen-Jing Li; Zhao Pan; Jia-Cai He; et al. (Chemical Engineering Journal, 2025)

Soil degradation: A global threat to sustainable use of black soils - Rui LI; Wenyou HU; Zhongjun JIA; Hanqiang LIU; Chao ZHANG; Biao HUANG; Shunhua YANG; Yuguo ZHAO; Yongcun ZHAO; Manoj K. SHUKLA; Miguel Angel TABOADA (Pedosphere, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

UPLC-HDMS revealed numerous novel compounds in soybean crude oil - Zhaohui Sun; Feng Dong; Rui Zhang; Xinyu Song; Xiaocai Huang; Yingran Dong; Xiaofei Jia; Shunian Luo; Ying Li; Maoqing Wang (Food Chemistry, 2025)

Gradient ethanol extracts of Coreopsis tinctoria buds: Chemical and in vitro fermentation characteristics - Shang Gao; Tiantian Li; Zhao-Rong Li; Bingwu Liao; Mouming Zhao; Chunxia Zhou; Donghui Luo; Rui-Bo Jia (Food Chemistry, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Physio-biochemical and molecular mechanisms of low nitrogen stress tolerance in peanut (Arachis hypogaea L.) - Xiangjun Kong; Rui Wang; Peipei Jia; Hengbin Li; Aziz Khan; Ali Muhammad; Sajid Fiaz; Qunce Xing; Zhiyong Zhang (Plant Molecular Biology, 2025)

Spatial Characteristics of the Plasma Spark Source Wavelet - Jia Wei; Xiaozhu Hao; Jing Feng; Rui Yang; Lei Xing; Huaishan Liu; Wei Wang; Zhiqiang Wu; Dong Zhang; Linwei Li (Journal of Ocean University of China, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Study on the evolution of ecological flow in river and its guarantee degree during different hydrological periods - Xue Chen; Qin Li; Zhuo Jia; Rui Xiao; Zhijin Cheng; Yuhao Peng (Journal of Cleaner Production, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Design method of simplified dynamic test model for high-rise building with underground structures considering nonlinear behavior similarity - Rui Wang; Zhi-Qian Dong; Gang Li; Ding-Hao Yu; Yao-Zhong Cui; Han Zhang; Jia-Long Li (Engineering Structures, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

Enhancing direct air carbon capture into microalgae: A membrane sparger design with carbonic anhydrase integration - Rui-Long Wang; Ming-Jia Li; Gregory J.O. Martin; Sandra E. Kentish (Algal Research, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Assessing the climatic niche changes and global invasion risk of Solanum elaeagnifolium in relation to human activities - Xin-Di Li; Yu Chen; Chun-Ling Zhang; Jia Wang; Xing-Jiang Song; Xian-Rui Zhang; Zhi-Hong Zhu; Gang Liu (Science of The Total Environment, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Recovery of low-concentration waste acid by electrodialysis: Modeling and validation - Feng-rui Li; Yu-xiang Jia; Meng Wang (Journal of Cleaner Production, 2024)

Bacterial cellulose aerogels with sensitive indication and high adsorption capacity for indoor formaldehyde removal - Wenjing Zeng; Hongli Fang; Juan Jia; Qingxuan Li; Zebao Rui (Journal of Environmental Chemical Engineering, 2024)

Effects of microplastics on soil physicochemical properties and vertical migration and transformation of chromium - Jia-li Li; Na-ying Li; Jia Ni; Rui-lin Wan; Jin-yan Yang (Journal of Environmental Chemical Engineering, 2024)

The influence of Cu2+ and Pb2+ on the characteristics of extracellular polymeric substances (EPSs) from Mucor mucedo and its relationship with pyrene biodegradation - Chunyun Jia; Xuqin Bai; Shiwei Wang; Yue Ding; Rui Liu; Xiaojun Li (Journal of Environmental Chemical Engineering, 2024)

Effects of ammonia energy ratio and PODE injection timing on combustion and emissions in a PODE/ammonia RCCI engine - Rui Ding; Yaopeng Li; Haoran Li; Yikang Cai; Ming Jia (Fuel, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Tailoring Na2FePO4F nanoparticles as the high-rate capability and Long-life cathode towards fast chargeable sodium-ion full batteries - Weihuang Wang; Shuhui Li; Yixin Jia; Dongqiang Cao; Rui Liu; Zheng Wang; Zicheng Xie; Lantian Zhang; Liangbing Wang (Chemical Engineering Journal, 2024)

Identification and validation of two quantitative trait loci showing pleiotropic effect on multiple grain-related traits in bread wheat (Triticum aestivum L.) - Wenjing Hu; Junchao You; Rui Yong; Die Zhao; Dongshen Li; Zunjie Wang; Jizeng Jia (Theoretical and Applied Genetics, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Neuroprotective Effect of a Multistrain Probiotic Mixture in SOD1G93A Mice by Reducing SOD1 Aggregation and Targeting the Microbiota-Gut-Brain Axis - Zikai Xin; Cheng Xin; Jia Huo; Qi Liu; Hui Dong; Rui Li; Yaling Liu (Molecular Neurobiology, 2024)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by the selective loss of motor neurons. A bidirectional communication system known as the “microbiota-gut-brain” axis has a regulatory function in neurodegenerative disorders. The impact of probiotics on ALS through the “microbiota-gut-brain” axis remains uncertain. A longitudinal investigation was conducted to examine the alterations in the structure of the ileum and colon in mutant superoxide dismutase 1 (SOD1 G93A ) transgenic mice models of ALS by using immunofluorescence and Western blotting. Subsequently, the mice were administered a multistrain probiotic mixture (LBE) or vehicle orally, starting from 60 days of age until the terminal stage of the disease. The effects of these agents on the behavior, gut microbiota, microbial metabolites, and pathological processes of the spinal and intestine of SOD1 G93A mice were analyzed, with a focus on exploring potential protective mechanisms. SOD1 G93A mice exhibit various structural abnormalities in the intestine. Oral administration of LBE improved the proinflammatory response, reduced aberrant superoxide dismutase 1 (SOD1) aggregation, and protected neuronal cells in the intestine and spinal cord of SOD1 G93A mice. Furthermore, LBE treatment resulted in a change in intestinal microbiota, an increase in short-chain fatty acid levels, and an enhancement in autophagy flux. SOD1 G93A mice exhibited various structural abnormalities in the intestine. LBE can improve the proinflammatory response, reduce aberrant SOD1 aggregation, and protect neuronal cells in the spinal cord and intestine of SOD1 G93A mice. The positive effect of LBE can be attributed to increased short-chain fatty acids and enhanced autophagy flux.

Sirtuin 7 ameliorates cuproptosis, myocardial remodeling and heart dysfunction in hypertension through the modulation of YAP/ATP7A signaling - Yu-Fei Chen; Rui-Qiang Qi; Jia-Wei Song; Si-Yuan Wang; Zhao-Jie Dong; Yi-Hang Chen; Ying Liu; Xin-Yu Zhou; Jing Li; Xiao-Yan Liu; Jiu-Chang Zhong (Apoptosis, 2024)

Real-time lettuce-weed localization and weed severity classification based on lightweight YOLO convolutional neural networks for intelligent intra-row weed control - Rui Hu; Wen-Hao Su; Jia-Le Li; Yankun Peng (Computers and Electronics in Agriculture, 2024)

Mechanisms of litter input changes on soil organic carbon dynamics: a microbial carbon use efficiency-based perspective - Jia Zeng; Xiangyang Li; Rui Song; Haoxuan Xie; Xiangnan Li; Weichao Liu; Hanyu Liu; Yaoyao Du; Miaoping Xu; Chengjie Ren; Gaihe Yang; Xinhui Han (Science of The Total Environment, 2024)

Unveiling the synergism and reaction pathway of ethyl acetate removal in DBD/absorption integrated reactor - Li-qiang Qi; Lin Huang; Jia-yue Lei; Rui Dai; Fan Du; Bo Wang; Jing-xin Li; Feng Liu (Process Safety and Environmental Protection, 2024)

Peering through the hedge: Multiple datasets yield insights into the phylogenetic relationships and incongruences in the tribe Lilieae (Liliaceae) - Deng-Feng Xie; Juan Li; Jia-Hui Sun; Rui-Yu Cheng; Yuan Wang; Bo-Ni Song; Xing-Jin He; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2024)

Synergistic effects of phosphorylation modification and protocatechuic acid copolymerization improve the physical and oxidation stability of high internal phase emulsion stabilized by perilla protein isolate - Qiaoli Zhao; Jinwei Li; Haili Qin; Rui Li; Kit Leong Cheong; Jianping Chen; Xiaofei Liu; Xuejing Jia; Bingbing Song; Zhuo Wang; Saiyi Zhong (Food Chemistry, 2024)

Screening and tentatively identifying of volatile hazards of desiccant and deoxidizer in food package - Hongyi Liu; Rui Fan; Siting Li; Hong Zhang; Zhou Chen; Aijin Ma; Yingmin Jia (Food Control, 2024)

Factors influencing nonstandard piezocone dissipation curves and interpreting the coefficient of consolidation - Rui Jia; Zhongping Wu; Yiqun Li; Huayang Lei (Computers and Geotechnics, 2024)

Polyaniline-coated sodium vanadate nanorods cathode boosting zinc ion dynamics in aqueous zinc-ion batteries - Rui Jia; Chengjie Yin; Bin Wang; Lan Li; Jinsong Hu (Chemical Engineering Journal, 2024)

Phase change thermal interface film with bicontinuous and textured filler network for efficient wearable heat dissipation - Jia-Qing Zhao; Xiang Wang; Xun-Rui Wang; Hong-Wei Zhao; Mei-Na Lu; Wayne-Qiang Xu; Hong-En Nian; Jin-Hong Li (Chemical Engineering Journal, 2024)

Monthly Runoff forecasting using A Climate‑driven Model Based on Two-stage Decomposition and Optimized Support Vector Regression - Zhuo Jia; Yuhao Peng; Qin Li; Rui Xiao; Xue Chen; Zhijin Cheng (Water Resources Management, 2024)

Analysis of factors affecting microbial degradation of cyanobacterial toxins based on theoretical calculations - Jianglong Ling; Ye Ruan; Congchao Xu; Di Liu; Bowen Shi; Yihong Yang; Zihao Jia; Tianyu Zhang; Mingxuan Guo; Rui Li; Xixi Li (Environmental Geochemistry and Health, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Water pollution control promotes sustainable water use in Yangtze River Economic Belt——from water footprint perspective - Ruining Jia; Zhongwen Yang; Rui Xia; Yan Chen; Lu Wang; Chen Yang; Hui Zhang; Qiang Hu; Xiang Li; Yingze Yin; Nixi Zhong; Chao Yan (Environment, Development and Sustainability, 2024)

Emulsion-filled surimi gel: A promising approach for enhancing gel properties, water holding capacity, and flavor - Qiaoli Zhao; Bin Zheng; Jinwei Li; Kit Leong Cheong; Rui Li; Jianping Chen; Xiaofei Liu; Xuejing Jia; Bingbing Song; Zhuo Wang; Saiyi Zhong (Trends in Food Science & Technology, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Disinfection of bacteria and viruses under near infrared light by tunable self-assembled nanomaterial NH2-MIL-101-xAu based on photothermal and photodynamic mechanisms - Nian Li; Zi-jian He; Jia-min Gan; Xing-rui Qi; Shu-nuo Bian; Yu-fang Chen; Bo Liu; Hua-jie Lai; Tao Jin (Journal of Environmental Chemical Engineering, 2024)

Portulaca oleracea L. polysaccharide ameliorates ulcerative colitis by regulating the immune system and gut microbiota - Yang Yang; Xiechen Zhou; Guiyan Jia; Hui Zhao; Yan Li; Junyang Cao; Zijian Guan; Rui Zhao (Food Bioscience, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Suppression the glucose-induced ferroptosis in endothelial cells by 4OI-loading exosomes hydrogel for the treatment of diabetic foot ulcer - Kuo Shen; Rui Zheng; Bangrui Yu; Hao Zhang; Peng Wang; Peng Zhao; Jijun Chen; Yixuan Yuan; Yuhang Wang; Kejia Wang; Yanhui Jia; Ruizhi Wang; et al. (Chemical Engineering Journal, 2024)

Effects of Spraying Allantoin at Different Stages on Inorganic Nitrogen Assimilation, Endogenous Hormones, Yield, and Quality of Sugar Beet in Saline-Alkali Land - Xin-Rui Yu; Jia-Nan Zhao; Yan-Long Zhuang; Ling-Hua Zhao; Chao Wang; Xiao-Fei Yang; Yu-Bo Wang; Cai-Feng Li (Sugar Tech, 2024)

Earthworms and Arbuscular Mycorrhizal Fungi Alleviated Salt Stress in Maize Seedlings by Regulating the Root Endodermis Diffusion Barrier - Binglei wang; Chong Wang; Lei Zhao; Xuelian Liu; Rui Xue; Jia Cao; Siping Li; Mengyao Guo; Huiying Huang (Journal of Plant Growth Regulation, 2024)

A nationwide characterization of organochlorine pesticides (OCPs) in livestock and poultry food products across China: Residual levels, origin and the associated health risks - Lu Chen; Yongzhong Qian; Xu Wang; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Chemosphere, 2024)

HT-2 toxin impairs porcine oocyte in vitro maturation through disruption of endomembrane system - Jia-Rui Li; Si-Le Wu; Lin-Lin Hu; Bi-Yun Liao; Shao-Chen Sun (Theriogenology, 2024)

A novel OsGST gene encoding 9glutathione reductase negatively regulates cadmium accumulation in rice - Rui Guo; Su Li; Yong Qiang Gao; Jia Tong He; Hao Yu Wang; Jin Chen; Jiu Huang; Ren Fang Shen; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Effects of anaerobic oxidation of methane (AOM) driven by iron and manganese oxides on methane emissions in constructed wetlands and underlying mechanisms - Ke Zhang; Rui Gan; Yangxingyue Li; Wei Chen; Dandan Ma; Jia Chen; Hongbing Luo (Chemical Engineering Journal, 2024)

In-situ forming carboxymethyl chitosan hydrogel containing Paeonia suffruticosa Andr. leaf extract for mixed infectious vaginitis treatment by reshaping the micro-biota - Shiami Jia; Shengting Huang; Rezhemu Jimo; Yongbu AXi; Yuanhui Lu; Ziling Kong; Jun Ma; Heran Li; Xiao Luo; Yan Qu; Kaijun Gou; Rui Zeng; et al. (Carbohydrate Polymers, 2024)

A multi-spatial scale analysis of anthropogenic nitrogen and phosphorus inputs in a large river basin: environmental effect and policy impact - Chenning Deng; Zeqian Zhang; Chaozheng Zhang; Rui Xu; Chong Nie; Qingjia Meng; Tiansen Zou; Hong Li; Jia Wu; Queping Yang (Regional Environmental Change, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Compositional analysis and quantitative evaluation of organic emissions from asphalt materials: Improvements and refinements - Rui Zhang; Naipeng Tang; Hongzhou Zhu; Yuan Xi; Huailei Cheng; Jia Liu; Rui Li (Journal of Cleaner Production, 2024)

Regulating the electronic state of SnO2@NiFe-LDH heterojunction: Activating lattice oxygen for efficient oxygen evolution reaction - Chaojie Yin; Fanghe Zhou; Chunliang Ding; Shengde Jin; Rui Zhu; Jiang Wu; Wenhao Li; Wu Yang; Jia Lin; Xinxia Ma; Jinao Deng; Zhongjun Zhao (Fuel, 2024)

Stochastic process is main factor to affect plateau river fish community assembly - Xiaoxuan Li; Qigong Xu; Rui Xia; Nan Zhang; Shuping Wang; Sen Ding; Xin Gao; Xiaobo Jia; Guangxia Shang; Xiaofei Chen (Environmental Research, 2024)

Oxygen-driven closing pore formation in coal-based hard carbon for low-voltage rapid sodium storage - Rui Ma; Yaxin Chen; Qian Li; Binyuan Zhang; Feifei Chen; Changyu Leng; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Integrated Rice–Fish Culture Alters the Bacterioplankton Community and Its Assembly Processes - Weixu Diao; Julin Yuan; Rui Jia; Yiran Hou; Liqiang Zhang; Bing Li; Jian Zhu (Fishes, 2024)
The rice–fish co-culture is an important model of carp farming in China; however, research on the dynamics and assembly of water bacterial communities in this system remains limited. Therefore, this study aimed to explore the dynamics and assembly of bacterial communities, as well as their correlation with environmental factors in paddy water. For these purposes, this study was divided into two groups: a rice–carp co-culture (WRC) group and a rice monoculture (WRM) group, with 20 rice fields in each group. After 60 days of farming, the concentrations of NH4+-N, NO2−-N, TN, and PO43− were significantly higher in the WRC group than those in the WRM group. Alpha diversity analysis showed that the Shannon index in the WRC group was significantly decreased compared with the WRM group. At the phylum level, the relative abundance of Actinobacteria significantly increased, while the relative abundance of Proteobacteria and Bacteroidetes significantly decreased in the paddy water of the WRC group. The neutral community model (NCM) indicated that a random process played a dominant role in the construction of bacterial communities in the two groups, and common carp cultivation increased migration rates, thereby affecting community assembly. The co-occurrence network displayed that common carp cultivation led to looser interactions between bacterial communities. In addition, the contents of nutrients significantly affected the abundance of bacteria in paddy water. In summary, carp cultivation decreased the diversity of bacteria and changed the relative abundance of dominant bacteria, thereby affecting the stability and assembly of bacterial communities.

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

Effects of Different Stocking Densities on the Growth, Antioxidant Status, and Intestinal Bacterial Communities of Carp in the Rice–Fish Co-Culture System - Weixu Diao; Rui Jia; Yiran Hou; Jianyou Gong; Liqiang Zhang; Bing Li; Jian Zhu (Fishes, 2024)
Common carp (Cyprinus carpio) is a freshwater fish commonly farmed in rice fields, yet there were few studies on the intestinal functions and microbial community structure of common carp in the rice–carp co-culture system. Therefore, this study aimed to explore the effects of different stocking densities on the growth, antioxidant status, and intestinal bacterial composition of common carp in this system. This study was divided into three different stocking densities, including low density (LD, 10 fish, 52.9 g/m2), medium density (MD, 20 fish, 105.8 g/m2), and high density (HD, 30 fish, 158.7 g/m2), with a culturing period of 60 days. The results indicated that HD treatment inhibited the growth of common carp, as evidenced by the reduced final weight, WG, and SGR. In serum, the TG content in the HD group and the Cor content in the MD group were significantly increased. Meanwhile, HD treatment induced oxidative stress, manifesting specifically as increased SOD and CAT activities in the intestine or serum while reducing Gpx, GSH, and T-AOC in the serum. The 16S rDNA analysis indicated that the Simpson and Shannon indices of intestinal microbiota in the HD group were significantly higher than those in the LD group. At the phylum level, Proteobacteria, Cyanobacteria, and Firmicutes were dominant microbial communities in two groups. In addition, there was a significant difference between the two groups in the abundances of Actinobacterota and Bifidobacterium. Based on growth performances, biochemical indicators, and microbial diversity in rice–carp co-culture, low density (52.9 g/m2) may be more suitable in the rice–carp co-culture systems. In summary, this study contributes to a better understanding of common carp response to different stocking densities in the rice–carp co-culture system.

Multi-objective optimization driven by preponderant individuals and symmetric sampling for operational parameter design in aluminum electrolysis process - Lizhong Yao; Jia Chen; Ling Wang; Rui Li; Haijun Luo; Jun Yi (Swarm and Evolutionary Computation, 2024)

Tracing the impacts of ecological water replenishment on the sources and transformation of groundwater nitrate through isotope and microbial analysis - Congchao Xu; Bowen Shi; Zihao Jia; Di Liu; Weiwu Hu; Chuanping Feng; Rui Li (Science of The Total Environment, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Experimental study on the hydrodynamic performance of a side-by-side box-membrane breakwater - Jing-Ping Wu; Chuan-Rui Li; Jing-Jing Qi; Xing-Yu Xu; Jia-Ning Li; Xiu-Xing Zhang; Qing Qin; Zhi-Rong Zhou (Ocean Engineering, 2024)

Catalytic ozonation of reverse osmosis concentrate from coking wastewater reuse by surface oxidation over Mn-Ce/γ-Al2O3: Effluent organic matter transformation and its catalytic mechanism - Rui Hu; Jia-Ying Li; Qiyi Yu; Sui-Qin Yang; Xinbo Ci; Bing Qu; Liwei Yang; Zheng-Qian Liu; Hongquan Liu; Jingjing Yang; Shiquan Sun; Yu-Hong Cui (Journal of Hazardous Materials, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Variations in antibiotic resistomes associated with archaeal, bacterial, and viral communities affected by integrated rice-fish farming in the paddy field ecosystem - Yiran Hou; Weixu Diao; Rui Jia; Wei Sun; Wenrong Feng; Bing Li; Jian Zhu (Environmental Research, 2024)

Effects of an anti-WSSV transgenic cyanobacterial oral agent on the development, reproduction, and physiology of Daphnia magna - Yupei Tong; Yang Xu; Wen Peng; Dingji Shi; Yuqing Li; Rui Jia (Journal of Applied Phycology, 2024)

Cadmium interacts with nitrogen level and nitrogen form to affect the growth of an invasive plant Alternanthera philoxeroides - Dan Li; Xiao-Gai Wang; Jia-Xin Yang; Yu-Fei Hu; Wen-Yue Lyu; Jun-Cai Xin; Rui Zhang; Zhi-Huan Chen; Chao Si (Aquatic Ecology, 2024)

A newly defined latest Carboniferous-Permian ridge subduction in the southern Altaids: Insights from adakitic, S-type, and I-type granitoids in the northern East Junggar (NW China) - Jingmin Gan; Wenjiao Xiao; Qigui Mao; Hao Wang; He Yang; Miao Sang; Xiaoliang Jia; Yin Liu; Zhiyong Zhang; Zhou Tan; Rui Li (International Geology Review, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Weakened hydrological oscillation period increased the frequency of river algal blooms - Qiang HU; Yan CHEN; Rui XIA; Xiaoyu LIU; Ruining JIA; Kai ZHANG; Xiaoxuan LI; Chao YAN; Yao WANG; Yingze YIN; Xiang LI; Junde MING (Water Research, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Bacterial community in the metal(loid)-contaminated marine vertical sediments of Jinzhou Bay: Impacts and adaptations - Yongbin Li; Rui Zhang; Guoqing Ma; Mingyi Shi; Yimei Xi; Xiaojun Li; Shaofeng Wang; Xiangfeng Zeng; Yongfeng Jia (Science of The Total Environment, 2024)

Integrated machine learning reveals aquatic biological integrity patterns in semi-arid watersheds - Lina Li; Rui Xia; Ming Dou; Kai Zhang; Yan Chen; Ruining Jia; Xiaoxuan Li; Jinghui Dou; Xiang Li; Qiang Hu; Hui Zhang; Nixi Zhong; et al. (Journal of Environmental Management, 2024)

The carbon dots with near-infrared electrochemiluminescence emission and low excitation potential for ultrasensitive analysis of microRNA-222 - Yu-Zhuo Guo; Rui Liu; Ying Zeng; Ye-Yu Liao; Jia-Li Liu; Ya-Qin Chai; Ruo Yuan (Chemical Engineering Journal, 2024)

Hollow glass microspheres incoporated conjugated microporous polymers composite aerogels for sustainable evaporation - Jiaxuan Zhou; Xiaoyin Cao; Yanju Jing; Jia Zhang; Hanxue Sun; Jiyan Li; Rui Jiao; An Li (Chemical Engineering Journal, 2024)

Proteomics Sequencing Reveals the Role of TGF-β Signaling Pathway in the Peripheral Blood of Offspring Rats Exposed to Fluoride - Fang-fang Yu; Shui-yuan Yu; Lei-zhen Duan; Shuo Yang; Xiang-bo Hou; Yu-hui Du; Ming-hui Gao; Juan Zuo; Lei Sun; Xiao-li Fu; Zhi-yuan Li; Hui Huang; et al. (Biological Trace Element Research, 2024)

Integrated rice-yellow catfish farming resulting in variations in the agricultural environment, rice growth performance, and soil bacterial communities - Yiran Hou; Zhaoxiong Yu; Rui Jia; Bing Li; Jian Zhu (Environmental Science and Pollution Research, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Exploring debris flow deposit morphology in river valleys: Insights from physical modeling experiments - Cong-Jiang Li; Yu-Xiang Hu; Gang Fan; Qing-Yang Zhu; Da-Rui Liu; Jia-Wen Zhou (Engineering Geology, 2024)

2D/2D ultrathin polypyrrole heterojunct aerogel with synergistic photocatalytic-photothermal evaporation performance for efficient water purification - Rui Li; Yong Li; Xiaohua Jia; Jin Yang; Xiao Miao; Dan Shao; Jun Wu; Haojie Song (Desalination, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Correction to: A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Engineering extracellular electron transfer to promote simultaneous brewing wastewater treatment and chromium reduction - Deguang Wu; Baocai Zhang; Sicheng Shi; Rui Tang; Chunxiao Qiao; Teng Li; Jichao Jia; Meiyi Yang; Xiaoguang Si; Yifei Wang; Xi Sun; Dongguang Xiao; et al. (Journal of Hazardous Materials, 2024)

Occurrence, distribution and ecological risk assessment of herbicide residues in cropland soils from the Mollisols region of Northeast China - Rui Li; Wenyou Hu; Hanqiang Liu; Biao Huang; Zhongjun Jia; Feng Liu; Yuguo Zhao; Khalid Saifullah Khan (Journal of Hazardous Materials, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

A new phthalides derivative pestalotiophthalide a with α-glucosidase inhibitory activity from Pestalotiopsis palmarum - Li-Bin Lin; Guang-Yu Bai; Xiang Zhao; Wei shi; Jia-Yao Hu; Jin-Ye Bai; Rui-Hua Wang; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Change of soil bacterial communities in chemically stabilized chromium contaminated soils in an accelerated aging experiment - Linying Yao; Yuning He; Peng Zhao; Zhihao Xie; Longfei Jiang; Danni Li; Yueqiao Liu; Rui Ma; Jianli Jia; Dayi Zhang (Journal of Environmental Chemical Engineering, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Cycloaspeptide H, a cyclopentapeptide from the endophytic fungus Penicillium virgatum - Ben-Chao Li; Liu-Xia Lv; Li-Li Huang; Jia-Tong Zhou; Xi-Shan Huang; Jun Li; Rui-Yun Yang; Wei-Feng Xu (Natural Product Research, 2024)

Speciation analysis and toxicity evaluation of arsenolipids—an overview focusing on sea food - Caiyan Li; Jing Chen; Zhuo Wang; Bingbing Song; Kit-Leong Cheung; Jianping Chen; Rui Li; Xiaofei Liu; Xuejing Jia; Sai-Yi Zhong (Archives of Toxicology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Performance analysis of microbial fuel cell - membrane bioreactor with reduced graphene oxide enhanced polypyrrole conductive ceramic membrane: Wastewater treatment, membrane fouling and microbial community under high salinity - Rui Wang; Hong You; Binghan Xie; Guoyu Zhang; Jing Zhu; Weirun Li; Xinan Dong; Qiqing Qin; Mengying Wang; Yi Ding; Haili Tan; Yuhong Jia; et al. (Science of The Total Environment, 2024)

Nano-selenium repaired the damage caused by fungicides on strawberry flavor quality and antioxidant capacity by regulating ABA biosynthesis and ripening-related transcription factors - Yuping Liu; Rui Liu; Feifei Li; Simin Yu; Yufan Nie; Jia-Qi Li; Canping Pan; Wentao Zhu; Zhiqiang Zhou; Jinling Diao (Pesticide Biochemistry and Physiology, 2024)

High titer (>100 g/L) ethanol production from pretreated corn stover hydrolysate by modified yeast strains - Rui Zhao; Hongshen Li; Qi Li; Zefang Jia; Shizhong Li; Ling Zhao; Shan Li; Yuwei Wang; Wenxin Fan; Ruoqi Ren; Zitong Yuan; Mengchan Yang; et al. (Bioresource Technology, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Microwave assisted synthesis of PQ-GDY@NH2-UIO-66(Zr) for improved photocatalytic removal of NO under visible light - Qingyu Yang; Shuangjun Li; Rui Liang; Lei Gao; Shao Zhang; Junfen Jia; Yiran Liu; Rundong Lyv; Guisheng Li; Shengxiong Xiao; Dieqing Zhang (Journal of Environmental Sciences, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Mechanistic insight into the adjuvant effect of co-exposure to ultrafine carbon black and high humidity on allergic asthma - Rui Deng; Jia Li; Haiping Wu; Mingpu Wang (Environmental Geochemistry and Health, 2023)

Telluribacter roseus sp. nov., Isolated from the Kumtag Desert Soil - Chu-Ying Feng; Jia-Rui Han; Chun-Yan Lu; Li Gu; Shuai Li; Wen-Hui Lian; Lei Dong; Wen-Jun Li (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Thermokarst lake susceptibility assessment using machine learning models in permafrost landscapes of the Arctic - Rui Wang; Lanlan Guo; Yuting Yang; Hao Zheng; Hong Jia; Baijian Diao; Hang Li; Jifu Liu (Science of The Total Environment, 2023)

Assessing resilience of sustainability to climate change in China's cities - Rui Zhao; Xia Li; Ying Wang; Zhenci Xu; Meiyu Xiong; Qian Jia; Fengting Li (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Dietary oregano essential oil supplementation alters meat quality, oxidative stability, and fatty acid profiles of beef cattle - Pengjia He; Yu Lei; Ke Zhang; Rui Zhang; Yunpeng Bai; Zeming Li; Li Jia; Jinping Shi; Qiang Cheng; Yannan Ma; Xiaoqiang Zhang; Lishan Liu; et al. (Meat Science, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

A machine learning-based method for identifying the meteorological field potentially inducing ozone pollution - Jia-Hui Tang; Si-Rui Pan; Lei Li; Pak-Wai Chan (Atmospheric Environment, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Recent innovations in microplastics and nanoplastics removal by coagulation technique: Implementations, knowledge gaps and prospects - Imran Ali; Xiao Tan; Yue Xie; Changsheng Peng; Juying Li; Iffat Naz; Zhipeng Duan; Peng Wan; Jiang Huang; Jia Liang; Zhu Rui; Yinlan Ruan (Water Research, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

A novel calcium peroxide/attapulgite-Fe(II) process for high concentration phosphate removal and recovery: Efficiency and mechanism - Jun Luo; Jia Peng; Zhenxing Zhong; Xuejun Long; Jiazhi Yang; Rui Li; Jun Wan (Journal of Environmental Management, 2023)

Renewable biocrude blends boost tribological properties and maintain fuel performance of diesel - Maojiong Cao; Yingxian Wang; Hugang Li; Jixiu Jia; Rui Li; Zhidan Liu (Chemical Engineering Journal, 2023)

Effects of Snail Bellamya purificata Farming at Different Stocking Densities on the Algal and Fungal Communities in Sediment - Yiran Hou; Mengmeng Zhou; Rui Jia; Wei Sun; Yanhong Yang; Xiongjian Huang; Bing Li; Jian Zhu (Fishes, 2023)
The snail Bellamya purificata is recognized as a potential bio-remediation species, and is commonly employed in polyculture to enhance resource utilization efficiency and realize culture environment regulation. In order to enrich the microbiome studies on elucidating the ecological effects of snail B. purificata farming, we assessed the effect of B. purificata farming activities, at varying stocking densities, on the algal and fungal communities in sediment. Four experimental groups were established in our study, each corresponding to a different stocking density: 0, 234.38, 468.75, and 937.5 g/m2, represented as CON, LD, MD, and HD, respectively. High-throughput sequencing based on ITS and 23S ribosomal RNA (rRNA) genes was employed to analyze the variations in algal and fungal communities under B. purificata farming activities at different stocking densities. B. purificata farming activities had no significant effect on the alpha diversities of fungal and algal communities, but significantly altered the compositions of fungal and algal communities in sediments, especially B. purificata farming activity at low stocking density. B. purificata farming activities at low stocking density could significantly increase the relative abundances of fungal genera Paraconiothyrium and Penicillium compared with the CON group. The promoting effect diminished with increasing density. B. purificata farming activities at low or medium stocking density also could enhance the relative abundances of algal genera Microchloropsis, Scenedesmus, and Auxenochlorella. Hence, B. purificata farming activity at low stocking density might be the optimum density to enhance resource utilization efficiency and minimize environmental pollution.

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Damage detection of foundation pile in high-pile wharf based on statistical high-order moment of dynamic response under regular wave excitation - Rui-hu Zhu; Qi-ming Wang; Jin-hai Zheng; Hai-kun Zeng; Jia-bao Zhang; Yan Hu; Cheng-ming Li (Ocean Engineering, 2023)

Integrated insight into the molecular mechanisms of selenium-modulated, MPP+-induced cytotoxicity in a Parkinson’s disease model - Wen Liu; Feiyang Zhang; Wu Liang; Kaixin Huang; Chenguang Jia; Jie Zhang; Xiang Li; Wei Wei; Rui Gong; Jincao Chen (Journal of Trace Elements in Medicine and Biology, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Featured immune characteristics of COVID-19 and systemic lupus erythematosus revealed by multidimensional integrated analyses - Xingwang Zhao; Mengjie Zhang; Yuying Jia; Wenying Liu; Shifei Li; Cuie Gao; Lian Zhang; Bing Ni; Zhihua Ruan; Rui Dong (Inflammation Research, 2023)

Elevation, bedrock exposure, land use, interbedded limestone and clastic rock, and vegetation coverage dominate the spatiotemporal variability of soil erosion in karst basin - Mei Chen; Jia-yong Gao; Hong-lian Chen; Jun Jing; Rui Li (Journal of Mountain Science, 2023)

Two new bibenzyls from Pleione grandiflora (Rolfe) Rolfe and their antioxidant activity - Wei Li; Jia-Rui Fu; Li-Jun Zheng; Lin Ni; Jun-Qing Liu; Jun-Wen Zhai; Zhuang Zhou; Sha-Sha Wu (Natural Product Research, 2023)

Non-steady state fluctuations in water levels exacerbate long-term and seasonal degradation of water quality in river-connected lakes - Yingze Yin; Rui Xia; Yan Chen; Ruining Jia; Nixi Zhong; Chao Yan; Qiang Hu; Xiang Li; Hui Zhang (Water Research, 2023)

Effects of dietary supplementation of Anabaena sp. PCC7120 expressing VP28 protein on survival and histopathology after WSSV infection in Macrobrachium nipponense - Yupei Tong; Jia Yang; Li Wang; Xiaoping Chi; Chan Zhu; Rong Yin; Le Zhang; Yaru Li; Chunyan Zhao; Rui Jia (Fish & Shellfish Immunology, 2023)

Cell Therapy for Androgenetic Alopecia: Elixir or Trick? - Yongcui Mao; Pinyan Liu; Jiayun Wei; Ye Xie; Qiuxia Zheng; Rui Li; Jia Yao (Stem Cell Reviews and Reports, 2023)
Androgenetic alopecia is the most common cause of hair loss aggravated by increased life pressure, tension, and anxiety. Although androgenetic alopecia (AGA) does not significantly effect physical health, it can have serious negative impact on the mental health and quality of life of the patient. Currently, the effect of medical treatment for AGA is not idealistic, stem cell-based regenerative medicine has shown potential for hair regrowth and follicle repair, but the long-term effect and mechanism of stem cell therapy is not quite explicit. In this review, we summarize the methods, efficacy, mechanism, and clinical progress of stem cell therapies for AGA by now, hope it will present a more comprehensive view in this topic. Graphical Abstract

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Fluorescence enhancement of surface plasmon coupled emission by Au nanobipyramids and its modulation effect on multi-wavelength radiation - Kai-Xin Xie; Rui-Ping Huo; Xiu-Li Song; Qiao-Ling Liu; Yue Jiang; Yu-Han Li; Lu-Lu Dong; Jia-Xin Cheng (Analytica Chimica Acta, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Potential of derivation of a series of C6–C14 1-alkene skeletal oxidation mechanisms on the basis of reaction rate rules - Shuai Huang; Yachao Chang; Ming Jia; Rui Hu; Tao Li (Fuel, 2023)

Characterizations of food-derived ellagic acid-Undaria pinnatifida polysaccharides solid dispersion and its benefits on solubility, dispersity and biotransformation of ellagic acid - Zhao-Rong Li; Rui-Bo Jia; Xueyuan Cai; Donghui Luo; Chong Chen; Mouming Zhao (Food Chemistry, 2023)

Different dietary fibers unequally remodel gut microbiota and charge up anti-obesity effects - Jia-Jia Wen; Ming-Zhi Li; Jie-Lun Hu; Jiang Wang; Zhi-Qiang Wang; Chun-Hua Chen; Jing-Rui Yang; Xiao-Jun Huang; Ming-Yong Xie; Shao-Ping Nie (Food Hydrocolloids, 2023)

Astrochronology and sedimentary noise modeling of Pliensbachian (Early Jurassic) sea-level changes, Paris Basin, France - Rui Zhang; David B. Kemp; Nicolas Thibault; Mads E. Jelby; Mingsong Li; Chunju Huang; Yu Sui; Zhixiang Wang; Dongyang Liu; Shizhen Jia (Earth and Planetary Science Letters, 2023)

Duox mediated ROS production inhibited WSSV replication in Eriocheir sinensis under short-term nitrite stress - Rui Jia; Xiaoling Dai; Yanfang Li; Xintong Yang; Xiuwen Min; Derun Quan; Peng Liu; Xin Huang; Jiachun Ge; Qian Ren (Aquatic Toxicology, 2023)

Insight into micropollutant abatement during ultraviolet light-emitting diode combined electrochemical process: Reaction mechanism, contributions of reactive species and degradation routes - Rui Hu; Sui-Qin Yang; Jia-Ying Li; Fengyi Sun; Zheng-Qian Liu; Jingjing Yang; Yu-Hong Cui; Beiping Zhang (Science of The Total Environment, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Immunoregulatory hydrogel decorated with Tannic acid/Ferric ion accelerates diabetic wound healing via regulating Macrophage polarization - Na Xu; Yuanping Gao; Zheng Li; Yu Chen; Menglong Liu; Jiezhi Jia; Rui Zeng; Gaoxing Luo; Jiangfeng Li; Yunlong Yu (Chemical Engineering Journal, 2023)

FHB resistance conferred by Fhb1 is under inhibitory regulation of two genetic loci in wheat (Triticum aestivum L.) - Guoqiang Li; Yang Yuan; Jiyang Zhou; Rui Cheng; Ruitong Chen; Xianmin Luo; Jinxing Shi; Heyu Wang; Boyang Xu; Youyu Duan; Jinkun Zhong; Xin Wang; et al. (Theoretical and Applied Genetics, 2023)

Porcine Mx proteins inhibit pseudorabies virus replication through interfering with early gene synthesis - Jing Chen; Jia-huan Hu; Rui-cong Sun; Xiao-han Li; Jing Zhou; Bin Zhou (Veterinary Microbiology, 2023)

Short-term effect of apparent temperature on daily hospitalizations for osteoporotic fractures in Beijing, China: A retrospective observational study - Shuai Lu; Xuejiao Liu; Yanlin Niu; Feng Li; Maoqi Gong; Yejun Zha; Qingchen Chao; Bo Lu; Baichao Zhang; Ning Li; Jia Chen; Qiyong Liu; et al. (Science of The Total Environment, 2023)

Southern Ocean warming and its climatic impacts - Wenju Cai; Libao Gao; Yiyong Luo; Xichen Li; Xiaotong Zheng; Xuebin Zhang; Xuhua Cheng; Fan Jia; Ariaan Purich; Agus Santoso; Yan Du; David M. Holland; et al. (Science Bulletin, 2023)

Bergamotane-type sesquiterpenes from the leaves and twigs of Illicium oligandrum and their anti-inflammatory activities - Wen-Rui Li; Jia-Ying Zhao; Mi Li; Xiao-Jing Wang; Guo-Zhu Su; Hai-Qiang Wang; Li Li; Guan-Hua Du; Ru-Bing Wang; Shuang-Gang Ma (Phytochemistry, 2023)

The hybridization origin of the Chinese endemic herb genus Notopterygium (Apiaceae): Evidence from population genomics and ecological niche analysis - Yun Jia; Mi-Li Liu; Jordi López-Pujol; Rui-Wen Jia; Yi-Xuan Kou; Ming Yue; Tian-Xia Guan; Zhong-Hu Li (Molecular Phylogenetics and Evolution, 2023)

A novel reduced graphene oxide/polypyrrole conductive ceramic membrane enhanced electric field membrane bioreactor: Mariculture wastewater treatment performance and membrane fouling mitigation - Rui Wang; Hong You; Zhipeng Li; Binghan Xie; Shaojie Qi; Jing Zhu; Qiqing Qin; Han Wang; Jinxu Sun; Yi Ding; Yuhong Jia; Feng Liu (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Endoplasmic reticulum stress regulates autophagic response that is involved in Saikosaponin a-induced liver cell damage - Ye-Feng Wang; Rui-Xia Ma; Bin Zou; Jia Li; Yao Yao; Juan Li (Toxicology in Vitro, 2023)

Phosphorus – The main limiting factor in riverine ecosystems in China - Yan Chen; Jie Chen; Rui Xia; Wenpan Li; Yuan Zhang; Kai Zhang; Shanlin Tong; Ruining Jia; Qiang Hu; Lu Wang; Xiaojiao Zhang (Science of The Total Environment, 2023)

Environmental risk of tailings pond leachate pollution: Traceable strategy for leakage channel and influence range of leachate - Bowen Shi; Xixi Li; Weiwu Hu; Beidou Xi; Shengrong Liu; Di Liu; Congchao Xu; Zihao Jia; Rui Li (Journal of Environmental Management, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Study on non-point source pollution characteristics under different spatial scales: a case study of Hanjiang River Basin, China - Ya-jiao Li; Jia-ping Wang; Zi-hang Zhang; Gai-rui Hao; Ya-fang Li; Jia-ke Li (Environmental Science and Pollution Research, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Effects of calcination on the environmental behavior of sediments by phosphorus speciation and interface characterization - Rui Xia; Pingzhou Duan; Rui Li; Lixin Jiao; Jia He; Shuai Ding; Xue Wu (Journal of Environmental Management, 2023)

Infant food production environments: A potential reservoir for vancomycin-resistant enterococci non-nosocomial infections - Zining Wang; Sihao Liao; Guanwen Huang; Mengyao Feng; Rui Yin; Lin Teng; Chenghao Jia; Yicheng Yao; Min Yue; Yan Li (International Journal of Food Microbiology, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Iron-based nanomaterials reduce cadmium toxicity in rice (Oryza sativa L.) by modulating phytohormones, phytochelatin, cadmium transport genes and iron plaque formation - Pingfan Zhou; Peng Zhang; Mengke He; Yu Cao; Muhammad Adeel; Noman Shakoor; Yaqi Jiang; Weichen Zhao; Yuanbo Li; Mingshu Li; Imran Azeem; Like Jia; et al. (Environmental Pollution, 2023)

Molecular regulation of immunity in tea plants - Lu Rui; Jia-yi Su; Tao Li; Jia-miao Sun; Guang-heng Wu (Molecular Biology Reports, 2023)

3D gravity anomaly inversion based on LinkNet - Hou-Pu Li; Rui Qi; Jia-Xin Hu; Yu-Xin Sun (Applied Geophysics, 2023)

Effect of Chronic Hydrogen Peroxide Exposure on Ion Transport in Gills of Common Carp (Cyprinus carpio) - Yating Mou; Bing Li; Yiran Hou; Rui Jia; Jian Zhu (Fishes, 2023)
High environmental hydrogen peroxide (H2O2) has been demonstrated to be toxic for fish. However, the response mechanism of fish to chronic H2O2 exposure is not yet well understood. Therefore, this study aimed to investigate the alteration in ion transport in gills and analyzed the potential response mechanism after chronic H2O2 exposure. The common carps were exposed to 0, 0.25, 0.50, and 1.00 mM of H2O2 for 14 days. The histopathological evaluation results indicated that H2O2 exposure caused incomplete gill filament structure. In the plasma, H2O2 exposure suppressed the potassium (K+) concentration but increased sodium (Na+) concentration. In the gills, the calcium (Ca2+) level was raised, but the K+ and chlorine (Cl−) levels were decreased after H2O2 exposure. After 14 days of exposure, H2O2 prompted the activities of Ca2+/Mg2+-ATPase and H+/K+-ATPase but suppressed Na+/K+-ATPase activity in the gills. Gene transcription analysis showed that the ion-regulation-related genes including nkaa and rhbg were downregulated after H2O2 exposure. In addition, H2O2 exposure upregulated the mRNA levels of cam and camk II, indicating that the Ca2+ singling pathway was activated. In conclusion, our data showed that chronic H2O2 exposure altered gill structure and disturbed ion transport, which further negatively affected the equilibrium of ions and osmotic pressure.

A national-scale distribution of organochlorine pesticides (OCPs) in cropland soils and major types of food crops in China: Co-occurrence and associated risks - Lu Chen; YongZhong Qian; Qi Jia; Rui Weng; Xinglian Zhang; Yun Li; Jing Qiu (Science of The Total Environment, 2023)

Sodium hydrosulfide alleviates aluminum toxicity in Brassica napus through maintaining H2S, ROS homeostasis and enhancing aluminum exclusion - Yan Yu; Jia Dong; Rui Li; Xue Zhao; Zonghe Zhu; Fugui Zhang; Kejin Zhou; Xianyong Lin (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Alleviative effects of astragaloside IV on cyclophosphamide-induced oxidative damage and immunosuppression in tilapia (Oreochromis niloticus) - Liping Cao; Jinliang Du; Rui Jia; Jiancao Gao; Zhijuan Nie; Nailin Shao; Quanjie Li; Haojun Zhu; Guojun Yin; Weidong Ding; Gangchun Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Interfacial fluoride engineering enabled robust LiF-rich solid electrolyte interphase to reduce active lithium loss in rechargeable lithium battery - Tianqi Jia; Geng Zhong; Sirong Lu; Xiaolong Ren; Yao Lv; Nanrui Li; Rui Yin; Guohuang Kang; Kangning Cai; Feiyu Kang; Yidan Cao (Chemical Engineering Journal, 2023)

Ameliorating C and N balance without loss of productivity by applying mulching measures in rainfed areas - Zihan Liu; Bingfan Wang; Zhaoyang Li; Chenxu Zhao; Rui Qian; Fangyuan Huang; Peng Zhang; Hui Li; ZhiKuan Jia (Agriculture, Ecosystems & Environment, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Oral administration of Synechococcus sp. PCC7942 trans-vp19 and trans-vp (19+28) genes improve the immune and antioxidant capacity in Procambarus clarkii under white spot syndrome virus stress - Jia Yang; Xiao-Ping Chi; Man Li; Wen-hui He; Rui Jia; Pei-Min He (Fish & Shellfish Immunology, 2023)

Characteristics of non-point source pollution based on monitoring experiment in the Yingwugou small watershed, China - Kai Peng; Jia-ke Li; Gai-rui Hao; Yi-wen Liu; Xiang Zhou; Wei-feng Xie (Ecohydrology & Hydrobiology, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Temperature-gradient-induced enhanced fog collection on polymer brush surfaces - Zheng-Hong Liang; Rui Feng; Jia-Min Wu; Dong Li; Fang Wang; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Lattice doping of Zn boosts oxygen vacancies in Co3O4 Nanocages: Improving persulfate activation via forming Surface-Activated complex - Mei-Mei Wang; Li-Juan Liu; Jia-Rui Xi; Ying Ding; Peng-Xi Liu; Liang Mao; Bing-Jie Ni; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Spatial distribution and quantitative source identification of nutrients and beneficial elements in the soil of a typical suburban area, Beijing - Qin-Rui Zhang; Sheng-Qiang Zhang; Yong Huang; Huan Li; Yan-Hui Jia; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Effects of Ran-GTP/importin β inhibition on the meiotic division of porcine oocytes - Yijing He; Jia Li; Lei Peng; Qiao Li; Yajie Chu; Qixin Lin; Jianjun Dai; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Nitrogen occurrence forms and bacterial community in sediment influenced by Bellamya purificata bioturbation - Yiyun Zhang; Yiran Hou; Rui Jia; Bing Li; Jian Zhu; Xianping Ge (Frontiers in Marine Science, 2022)
Endogenous water pollution and excessive nitrogen in ponds have always been prominent problems threatening aquaculture. To solve this problem, a 70-day indoor simulation experiment was conducted. The snail Bellamya purificata was stocked at four different densities: 0, 15, 30, and 60 individuals/tank, represented as CON (control), LD (low density), MD (medium density), and HD (high density), respectively, to investigate the effects of B. purificata on the nitrogen occurrence forms and bacterial communities in the sediment. At the end of the experiment, the nitrate concentration was significantly higher, while the total nitrogen content was significantly lower in the MD group than in the other three groups. Ammonia monooxygenase activity was significantly lower in the CON group than in the other three groups, and hydroxylamine oxidase activity was significantly higher in the HD group than in the other three groups. The CON and MD groups showed the highest and lowest values in nitrate reductase activity, respectively. The hydroxylamine reductase activity decreased significantly with increasing density. Through 16S ribosomal RNA (rRNA) high-throughput sequencing, significantly affected bacterial communities by B. purificata were found. Alpha diversity results showed that, a significantly lower Shannon index was observed in the MD group than in the other three groups. The LD and MD groups showed the highest and lowest Chao1 index values, respectively. Phyla Nitrospinae and family Nitrosomonadaceae were significantly enriched in the HD and MD groups, respectively. Redundancy analysis (RDA) indicated a significant correlation between differential bacterial taxa and TN content. Predicted functional analysis based on FAPROTAX (Functional annotation of prokaryotic taxa) database showed that functional groups aerobic ammonia oxidation and aerobic nitrite oxidation were significantly enriched in the MD group. Overall, B. purificata significantly altered the bacterial community composition, increased hydroxylamine oxidase and ammonia monooxygenase activities, enhanced the bacterial nitrification process, and promoted the transformation of total nitrogen to nitrate. Moreover, B. purificata stocked at 30 and 60 individuals/tank appeared to have a significant promotion effect on the bacterial community and nitrogen occurrence forms in the sediment. Hence, co-culturing B. purificata may be a feasible and effective ecological restoration method to alleviate excess nitrogen and reduce water eutrophication.

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Compounding soils to improve cropland quality: A study based on field experiments and model simulations in the loess hilly-gully region, China - Yun-xin Huang; Zheng-jia Liu; Yan-sui Liu; Yu-rui Li; Xue-qi Liu (Journal of Mountain Science, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Treating performance of a commercial-scale constructed wetland system for aquaculture effluents from intensive inland Micropterus salmoides farm - Bing Li; Rui Jia; Yiran Hou; Jian Zhu (Frontiers in Marine Science, 2022)
In intensive inland fish farming, discharge of untreated effluents adversely affects adjacent water bodies and causes water pollution. Thus, it is highly necessary to treat the effluents from inland fish farm. In this study, we built a commercial-scale integrated constructed wetland (CW) system with vertical subsurface flow, and monitored the purifying effect. During fish farming and discharge of effluents periods, the water samples were collected to detected the total nitrogen (TN), total phosphorus (TP), ammonia nitrogen (NH 4 + -N), nitrate nitrogen (NO 3 - -N), nitrite nitrogen (NO 2 - -N) and chemical oxygen demand (COD Mn ). Results showed that the system was stable and significantly improved water quality from fish pond. During the fish farming period, the removal efficiency for TN, TP, NH 4 + -N, NO 3 - -N, NO 2 - -N, and COD was 24.93–43.72%, 61.92–72.18%, 56.29–68.63%, 56.66–64.81%, 56.42–64.19% and 28.37–42.79%, respectively. Similarly, these parameters were also markedly decreased by the integrated CW system during sewage discharge period, and the average total removal rate for TN, TP, NH 4 + -N, NO 3 - -N, NO 2 - -N, and COD was 50.24%, 64.48%, 61.36%, 62.65%, 56.16% and 37.32%, respectively. It was worth noting that three key parameters for effluents detection TN, TP and COD values were below the threshold values of water quality of Class II in freshwater sewage discharge standard of China (SCT9101-2007). In conclusion, this study evidently demonstrated that application of CW system was an environmental sustainable sewage treatment strategy in intensive inland fish farming.

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Alterations in gut microbiota affect behavioral and inflammatory responses to methamphetamine in mice - Simin Lai; Jing Wang; Biao Wang; Rui Wang; Guodong Li; Yuwei Jia; Teng Chen; Yanjiong Chen (Psychopharmacology, 2022)

Longitalea arenae gen. nov., sp. nov. and Longitalea luteola sp. nov., two new members of the family Chitinophagaceae isolated from desert soil - Shuai Li; Lei Dong; Jia-Rui Han; Guo-Yuan Shi; Chun-Yan Lu; Lu Xu; Wen-Hui Lian; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Wen-Jun Li (Archives of Microbiology, 2022)

Development and perspectives of rapid detection technology in food and environment - Xue-Xia Jia; Shuang Li; Dian-Peng Han; Rui-peng Chen; Zi-Yi Yao; Bao-an Ning; Zhi-Xian Gao; Zhen-Chuan Fan (Critical Reviews in Food Science and Nutrition, 2022)

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Aberrant Gene Expression of Selenoproteins in Chicken Spleen Lymphocytes Induced by Mercuric Chloride - Jia-Hong Chu; Yu-Xue Yan; Xue-Wei Chen; Pei-Chao Gao; Lan-Xin Li; Rui-Feng Fan (Biological Trace Element Research, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Alkaloids constituents from the roots of Phragmites australis (Cav.) Trin. ex Steud. with their cytotoxic activities - Ying Chen; Li Li; Li-Rui Jiang; Jia-Yin Tan; Li-Na Guo; Xiao-Li Wang; Wei Dong; Wen-Bao Wang; Ji-Kai Sun; Bo Song (Natural Product Research, 2022)

Microseismic signal denoising by combining variational mode decomposition with permutation entropy - Zhang Xing-Li; Cao Lian-Yue; Chen Yan; Jia Rui-Sheng; Lu Xin-Ming (Applied Geophysics, 2022)

A Reliable Murine Model of Disseminated Infection Induced by Talaromyces Marneffei - Juan He; Jia-Sheng Li; Hong-Yan Xu; Yi-Qun Kuang; Jun Li; Hong-Bin Li; Zhe Li; Hui-Ling Zhou; Rui-Rui Wang; Yu-Ye Li (Mycopathologia, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

Dimeric hexylitaconic acids from the marine-derived fungus Aspergillus welwitschiae CUGBMF180262 - Jiahui Han; Na Yang; Shangzhu Wei; Jia Jia; Rui Lin; Jiangpeng Li; Hongkai Bi; Fuhang Song; Xiuli Xu (Natural Product Research, 2022)

Four new indole alkaloids from the roots of Isatis tinctoria - Dongdong Zhang; Yu Sun; Yanhong Shi; Ximin Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2022)

Air pollution increased risk of reproductive system diseases: a 5-year outcome analysis of different pollutants in different seasons, ages, and genders - Ya Li; Juan Du; Shanshan Lin; Huihui He; Rui Jia; Weihong Liu (Environmental Science and Pollution Research, 2022)

Characterization on the P-associated and agronomic traits as well as associated molecular processes in wheat under Pi deprivation condition - Ying-Jia Zhao; Xin-Yang Bai; Rui-Ze Lin; Fang-fang Li; Kai Xiao (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Risk assessment of non-point source pollution based on landscape pattern in the Hanjiang River basin, China - Yi-wen Liu; Jia-ke Li; Jun Xia; Gai-rui Hao; Fang-Yenn Teo (Environmental Science and Pollution Research, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Numerical modeling of 3D DC resistivity method in the mixed space-wavenumber domain - Shi-Kun Dai; Jia-Xuan Ling; Qing-Rui Chen; Kun Li; Qian-Jiang Zhang; Dong-Dong Zhao; Ying Zhang (Applied Geophysics, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

Herbidospora solisilvae sp. nov., a novel cellulose-degrading actinobacterium isolated from forest soil - Mingying Yu; Rui Zhou; Jingjing Li; Liyuan Han; Han Wang; Siyu Zhang; Junwei Zhao; Xiangjing Wang; Jia Song; Wensheng Xiang (Antonie van Leeuwenhoek, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Rescue effects of Se-enriched rice on physiological and biochemical characteristics in cadmium poisoning mice - Yang Su; Ling Li; Muhammad Umer Farooq; Xin Huang; Tengda Zheng; Yu Jie Zhang; Hla Hla Ei; Faiz Hussain Panhwar; Zhichen Tang; Rui Zeng; Yuanke Liang; Xiaoying Ye; et al. (Environmental Science and Pollution Research, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

The regional difference in engineering-control and tillage factors of Chinese Soil Loss Equation - Rui-yin Chen; Dong-chun Yan; An-bang Wen; Zhong-lin Shi; Jia-cun Chen; Yuan Liu; Tai-li Chen (Journal of Mountain Science, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Indole alkaloid glycosides from Isatis tinctoria roots - Dongdong Zhang; Kang Du; Yitian Zhao; Songshan Shi; Yingchun Wu; Qi Jia; Kaixian Chen; Yiming Li; Rui Wang (Natural Product Research, 2021)

Identification and expression analysis of caffeoyl-coenzyme A O-methyltransferase family genes related to lignin biosynthesis in tea plant (Camellia sinensis) - Shi-Jia Lin; Ya-Zhuo Yang; Rui-Min Teng; Hao Liu; Hui Li; Jing Zhuang (Protoplasma, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

Effects of shading on lignin biosynthesis in the leaf of tea plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Shi-Jia Lin; Hao Liu; Jing Zhuang (Molecular Genetics and Genomics, 2021)

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

New potential strains for controlling Spodoptera frugiperda in China: Cordyceps cateniannulata and Metarhizium rileyi - Ye-Ming Zhou; Wen Xie; Jia-Qin Ye; Tao Zhang; Ding-Yin Li; Jun-Rui Zhi; Xiao Zou (BioControl, 2020)

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

Quantitative assessment of non-point source pollution load of PN/PP based on RUSLE model: a case study in Beiluo River Basin in China - Gai-rui Hao; Jia-ke Li; Shu Li; Kang-bin Li; Zi-hang Zhang; Huai-en Li (Environmental Science and Pollution Research, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

Improvement of water quality in the Pearl River Estuary, China: a long-term (2008–2017) case study of temporal-spatial variation, source identification and ecological risk of heavy metals in surface water of Guangzhou - Yan-ping Zhao; Rui Wu; Jin-li Cui; Shu-chai Gan; Jia-chuan Pan; Peng-ran Guo (Environmental Science and Pollution Research, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

Comparative study on the bioaccumulation of lead, cadmium and nickel and their toxic effects on the growth and enzyme defence strategies of a heavy metal accumulator, Hydrilla verticillata (L.f.) Royle - Hong Zhang; Ling-Lei Zhang; Jia Li; Min Chen; Rui-Dong An (Environmental Science and Pollution Research, 2020)

Anfibatide Preserves Blood–Brain Barrier Integrity by Inhibiting TLR4/RhoA/ROCK Pathway After Cerebral Ischemia/Reperfusion Injury in Rat - Peng Gong; Rui Li; Hui-Yu Jia; Zheng Ma; Xiao-Yi Li; Xiang-rong Dai; Sheng-Yong Luo (Journal of Molecular Neuroscience, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Improvement and application research of the SRM in alpine regions - Gai-rui Hao; Jia-ke Li; Kang-bin Li; Kang Huang; Jia-bao Song; Huai-en Li (Environmental Science and Pollution Research, 2019)

The complete chloroplast genome of Saxifraga sinomontana (Saxifragaceae) and comparative analysis with other Saxifragaceae species - Yan Li; Liukun Jia; Zhihua Wang; Rui Xing; Xiaofeng Chi; Shilong Chen; Qingbo Gao (Brazilian Journal of Botany, 2019)
Saxifraga sinomontana J.-T. Pan & Gornall belongs to Saxifraga sect. Ciliatae subsect. Hirculoideae , a lineage containing ca. 110 species whose phylogenetic relationships are largely unresolved due to recent rapid radiations. Analyses of complete chloroplast genomes have the potential to significantly improve the resolution of phylogenetic relationships in this young plant lineage. The complete chloroplast genome of S. sinomontana was de novo sequenced, assembled and then compared with that of other six Saxifragaceae species. The S. sinomontana chloroplast genome is 147,240 bp in length with a typical quadripartite structure, including a large single-copy region of 79,310 bp and a small single-copy region of 16,874 bp separated by a pair of inverted repeats (IRs) of 25,528 bp each. The chloroplast genome contains 113 unique genes, including 79 protein-coding genes, four rRNAs and 30 tRNAs, with 18 duplicates in the IRs. The gene content and organization are similar to other Saxifragaceae chloroplast genomes. Sixty-one simple sequence repeats were identified in the S. sinomontana chloroplast genome, mostly represented by mononucleotide repeats of polyadenine or polythymine. Comparative analysis revealed 12 highly divergent regions in the intergenic spacers, as well as coding genes of matK , ndhK , accD , cemA , rpoA , rps19 , ndhF , ccsA , ndhD and ycf1 . Phylogenetic reconstruction of seven Saxifragaceae species based on 66 protein-coding genes received high bootstrap support values for nearly all identified nodes, suggesting a promising opportunity to resolve infrasectional relationships of the most species-rich section Ciliatae of Saxifraga .

Filler improvement and purification effects of constructed rapid infiltration facility - Rui-song Zhao; Jia-ke Li; Chao Guo; Fan Li; Huai-en Li (Environmental Science and Pollution Research, 2019)

Wind and sand control by an oasis protective system: a case from the southeastern edge of the Tengger Desert, China - Yun-hu Xie; Xiao-hong Dang; Zhong-ju Meng; Hong-tao Jiang; Xiao-jia Li; Rui-ping Zhou; Dan-dan Zhou; Xiao-xi Liu; Jing Ding; Xue-qin Wu; Yu-hao Wang; Chun-xing Hai; et al. (Journal of Mountain Science, 2019)

De Novo Assembled Transcriptome Analysis and Identification of Genic SSR Markers in Red-Flowered Strawberry - Yan Ding; Li Xue; Rui-xue Guo; Gang-jun Luo; Yu-tong Song; Jia-jun Lei (Biochemical Genetics, 2019)

Depositional facies and stratal cyclicity of carbonate successions in the Yingshan and Yijianfang Group (Lower-Middle Ordovician) in Yuejin-Tuoputai Region, Tarim Basin, NW China - Cunli Jiao; Zhao Xue-Qin; Rui Zhao; Li Hui-Li; Liu Tian-Jia; Zhao Jia-Hui (Carbonates and Evaporites, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Genomic characterization and pathogenicity of porcine deltacoronavirus strain CHN-HG-2017 from China - Meng-Jia Zhang; De-Jian Liu; Xiao-Li Liu; Xing-Yi Ge; Anan Jongkaewwattana; Qi-Gai He; Rui Luo (Archives of Virology, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Energy-Based Brittleness Index and Acoustic Emission Characteristics of Anisotropic Coal Under Triaxial Stress Condition - Jun Zhang; Chi Ai; Yu-wei Li; Ming-guang Che; Rui Gao; Jia Zeng (Rock Mechanics and Rock Engineering, 2018)

Fast 3D forward modeling of the magnetic field and gradient tensor on an undulated surface - Kun Li; Long-Wei Chen; Qing-Rui Chen; Shi-Kun Dai; Qian-Jiang Zhang; Dong-Dong Zhao; Jia-Xuan Ling (Applied Geophysics, 2018)

Characterization of clinical features and outcome for human-to-human transmitted severe fever with thrombocytopenia syndrome - Bei Jia; Weihua Wu; Rui Huang; Guiyang Wang; Peixin Song; Yang Li; Yong Liu; Yali Xiong; Xiaomin Yan; Yingying Hao; Juan Xia; Zhaoping Zhang; et al. (Infectious Diseases, 2018)

Time is nothing: emotional consistency of autobiographical memory and its neural basis - Rui Xu; Juan Yang; Chunliang Feng; Haiyan Wu; Ruiwang Huang; Qiuli Yang; Zhihao Li; Pengfei Xu; Ruolei Gu; Yue-jia Luo (Brain Imaging and Behavior, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Effects of Rhizoma Alismatis extract on biochemical indices and adipose gene expression in oleic acid-induced hepatocyte injury in Jian carp (Cyprinus carpio var. Jian) - Jinliang Du; Rui Jia; Li-ping Cao; Weidong Ding; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2018)

Least squares reverse-time migration in the pseudodepth domain and reservoir exploration - Xiao-Dong Sun; Yan-Rui Jia; Min Zhang; Qing-Yang Li; Zhen-Chun Li (Applied Geophysics, 2018)

Identification of blasting vibration and coal-rock fracturing microseismic signals - Xing-Li Zhang; Rui-Sheng Jia; Xin-Ming Lu; Yan-Jun Peng; Wei-Dong Zhao (Applied Geophysics, 2018)

A Fluorescent Sensor of 3-Aminobenzeneboronic Acid Functionalized Hydrothermal Carbon Spheres for Facility Detection of L-tryptophan - Rui Zhang; Li-Xia Wang; Yun-Di Zhang; Chun-Hua Ge; Jia-Ping Wang; Ying Zhang; Xiang-Dong Zhang (Journal of Fluorescence, 2018)

Re-engineering the two-component systems as light-regulated in Escherichia coli - Siya Ma; Siwei Luo; Li Wu; Zhi Liang; Jia-Rui Wu (Journal of Biosciences, 2017)

Variable-grid reverse-time migration of different seismic survey data - Xiao-Dong Sun; Zhen-Chun Li; Yan-Rui Jia (Applied Geophysics, 2017)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Genetic and transcriptomic analyses of lignin- and lodging-related traits in Brassica napus - Lijuan Wei; Hongju Jian; Kun Lu; Nengwen Yin; Jia Wang; Xiujian Duan; Wei Li; Liezhao Liu; Xinfu Xu; Rui Wang; Andrew H. Paterson; Jiana Li (Theoretical and Applied Genetics, 2017)

Comparison of dust emissions, transport, and deposition between the Taklimakan Desert and Gobi Desert from 2007 to 2011 - SiYu Chen; JianPing Huang; JingXin Li; Rui Jia; NanXuan Jiang; LiTai Kang; XiaoJun Ma; TingTing Xie (Science China Earth Sciences, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Reduction of soil-borne pathogen Fusarium solani reproduction in soil enriched with phenolic acids by inoculation of endophytic fungus Phomopsis liquidambari - Xing-Guang Xie; Chuan-Chao Dai; Xiao-Gang Li; Jia-Rui Wu; Qing-Qian Wu; Xing-Xiang Wang (BioControl, 2017)

Molecular cloning and characterization of α-amylase/subtilisin inhibitor from rhizome of Ligusticum chuanxiong - Ji-hua Yu; Yang-yang Li; Mian Xiang; Jian-quan Zhu; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2017)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

Assessing spatial likelihood of flooding hazard using naïve Bayes and GIS: a case study in Bowen Basin, Australia - Rui Liu; Yun Chen; Jianping Wu; Lei Gao; Damian Barrett; Tingbao Xu; Linyi Li; Chang Huang; Jia Yu (Stochastic Environmental Research and Risk Assessment, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Dust aerosol properties and radiative forcing observed in spring during 2001–2014 over urban Beijing, China - Xingna Yu; Rui Lü; K. Raghavendra Kumar; Jia Ma; Qiuju Zhang; Yilun Jiang; Na Kang; Suying Yang; Jing Wang; Mei Li (Environmental Science and Pollution Research, 2016)

Elevated IL-6 and TNF-α Levels in Cerebrospinal Fluid of Subarachnoid Hemorrhage Patients - Wei Wu; Yi Guan; Gang Zhao; Xi-Jia Fu; Tie-Zhu Guo; Yue-Ting Liu; Xin-Liang Ren; Wei Wang; Han-Rui Liu; Yun-Qian Li (Molecular Neurobiology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

A Study of 2,3,7,8-Tetrachlorodibenzo-p-dioxin Induced Liver Injury in Jian Carp (Cyprinus carpio var. Jian) Using Precision-Cut Liver Slices - Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Rui Jia; Guo-Jun Yin (Bulletin of Environmental Contamination and Toxicology, 2016)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

A Controlled Study of Alprostadil Liposomal Preparation in the Treatment of Blue Toe Syndrome - Hai-lin Xi; Rui Li; Zhi-long Tian; Su Feng; Gao-Lei Jia (Cell Biochemistry and Biophysics, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Degradation of recalcitrant aliphatic and aromatic hydrocarbons by a dioxin-degrader Rhodococcus sp. strain p52 - Hai-Yan Yang; Rui-Bao Jia; Bin Chen; Li Li (Environmental Science and Pollution Research, 2014)

Seohaeicola westpacificensis sp. nov., A Novel Member of Genera Seohaeicola Isolated from Deep West Pacific Sea Water - Shuhui Xian; Rui Zhang; Jia Sun; Yi Chen; Wenchao Deng; Shuhui Li; Nianzhi Jiao (Current Microbiology, 2014)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Genomewide analysis of the chitinase gene family in Populus trichocarpa - CONG JIANG; RUI FANG HUANG; JIA LIANG SONG; MIN REN HUANG; LI AN XU (Journal of Genetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

An approach for the critical coagulation concentration estimation of polydisperse colloidal suspensions of soil and humus - Mingyun Jia; Hang Li; Hualing Zhu; Rui Tian; Xiaodan Gao (Journal of Soils and Sediments, 2013)

Exogenous hydrogen sulfide attenuates diabetic myocardial injury through cardiac mitochondrial protection - Xin Zhong; Leihong Wang; Yuwen Wang; Shiyun Dong; Xiaoning Leng; Jing Jia; Yajun Zhao; Hulun Li; Xinying Zhang; Changqing Xu; Guangdong Yang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2012)

ST13, a proliferation regulator, inhibits growth and migration of colorectal cancer cell lines - Rui Bai; Zhong Shi; Jia-wei Zhang; Dan Li; Yong-liang Zhu; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

Genetic characterization of Aleutian mink disease viruses isolated in China - Yanwu Li; Juan Huang; Yun Jia; Yijun Du; Ping Jiang; Rui Zhang (Virus Genes, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Effects of a non-selective TRPC channel blocker, SKF-96365, on melittininduced spontaneous persistent nociception and inflammatory pain hypersensitivity - Jing Ding; Jia-Rui Zhang; Yan Wang; Chun-Li Li; Dan Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Proteomics analysis of plasma membrane from liver sinusoidal endothelial cells after partial hepatectomy by an improved two-dimensional electrophoresis - Xuanwen Li; Li Xiong; Chunliang Xie; Jia Cao; Huobao Deng; Yong Lin; Rui Cao; Jianglin Li; Ping Chen; Songping Liang (Molecular and Cellular Biochemistry, 2010)

Chemical constituents of Gentiana macrophylla Pall. - Zhi-Bo Jiang; Hong-Li Liu; Xiao-Qing Liu; Ji-Ning Shang; Jia-Rui Zhao; Cheng-Shan Yuan (Natural Product Research, 2010)

Photocatalytic degradation of organic dyes by Er3+:YAlO3/TiO2 composite under solar light - Jun Wang; Yingpeng Xie; Zhaohong Zhang; Jia Li; Chengwu Li; Liquan Zhang; Zhiqiang Xing; Rui Xu; Xiangdong Zhang (Environmental Chemistry Letters, 2010)

NMDA receptor antagonist MK-801 reduces neuronal damage and preserves learning and memory in a rat model of traumatic brain injury - Rui-Zhang Han; Jin-Jia Hu; Yuan-Chi Weng; Ding-Feng Li; Yi Huang (Neuroscience Bulletin, 2009)

Activity of the Antimicrobial Peptide and Thanatin Analog S-thanatin on Clinical Isolates of Klebsiella pneumoniae Resistant to Conventional Antibiotics with Different Structures - Guo-Qiu Wu; Jia-Xuan Ding; Lin-Xian Li; Hai-liang Wang; Rui Zhao; Zi-Long Shen (Current Microbiology, 2009)

Development and characterization of new microsatellite loci from Chinese mitten crab (Eriocheir sinensis) - Rui X. Mao; Ying Y. Zhao; Fu J. Liu; Zhi Y. Jia; Ning Hou; Yu M. Chang; Cui Y. Lu; Li Q. Liang; Xiao W. Sun (Conservation Genetics, 2009)

Genome-wide Comparisons of Gene Expression for Yield Heterosis in Maize - Bo Li; Deng-Feng Zhang; Guan-Qing Jia; Jing-Rui Dai; Shou-Cai Wang (Plant Molecular Biology Reporter, 2009)

Complete genomic sequence analyses of Turnip mosaic virus basal-BR isolates from China - Hong-Yan Wang; Jin-Liang Liu; Rui Gao; Jia Chen; Yun-Hua Shao; Xiang-Dong Li (Virus Genes, 2009)

Tumor-inhibitory and liver-protective effects of Phellinus igniarius extracellular polysaccharides - Wei Dong; Li Ning; Wei-dong Lu; Cui-cui Li; Rui-peng Chen; Xiao-ning Jia; Lin Wang; Li-zhong Guo (World Journal of Microbiology and Biotechnology, 2009)

TRANSPARENT TESTA 12 genes from Brassica napus and parental species: cloning, evolution, and differential involvement in yellow seed trait - You-Rong Chai; Bo Lei; Hua-Lei Huang; Jia-Na Li; Jia-Ming Yin; Zhang-Lin Tang; Rui Wang; Li Chen (Molecular Genetics and Genomics, 2009)

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Rapid Quantitative Detection of Vibrio parahaemolyticus in Seafood by MPN-PCR - Xiaoyan Luan; Jixiang Chen; Yu Liu; Yun Li; Juntao Jia; Rui Liu; Xiao-Hua Zhang (Current Microbiology, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

AtMTM1, a novel mitochondrial protein, may be involved in activation of the manganese-containing superoxide dismutase in Arabidopsis - Zhao Su; Mao-Feng Chai; Ping-Li Lu; Rui An; Jia Chen; Xue-Chen Wang (Planta, 2007)

A novel drought-inducible gene, ATAF1, encodes a NAC family protein that negatively regulates the expression of stress-responsive genes in Arabidopsis - Ping-Li Lu; Nai-Zhi Chen; Rui An; Zhao Su; Bi-Shu Qi; Fei Ren; Jia Chen; Xue-Chen Wang (Plant Molecular Biology, 2006)

The wheat TaGI1, involved in photoperiodic flowering, encodesan Arabidopsis GI ortholog - Xiang Yu Zhao; Mao Sen Liu; Jia Rui Li; Chun Mei Guan; Xian Sheng Zhang (Plant Molecular Biology, 2005)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)